Display device, optical film, and method for manufacturing optical film

By using an optical film containing cellulose acetate with a specific degree of substitution and metal oxide or metal salt fillers with a specific aspect ratio in a display device, the problem of insufficient visibility and impact resistance after the display device is thinned is solved, and the effects of high impact resistance and folding resistance are achieved.

CN120813983APending Publication Date: 2025-10-17KONICA MINOLTA INC

Patent Information

Application Number
CN202480015301.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-02-28
Filing Date
2024-01-31
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

In the process of thin-filming, existing display devices have difficulty in achieving both good visibility and impact resistance. In particular, when color filters are used instead of circular polarizers, the display devices have insufficient impact resistance and folding resistance.

Method used

An optical film containing cellulose acetate with a specific degree of acetyl substitution and a metal oxide or metal salt filler with a specific aspect ratio is used, combined with an appropriate indentation elastic modulus and a stacking sequence to form a display device with high impact resistance and folding resistance.

Benefits of technology

The display device maintains good visibility and impact resistance during the thin film process, and even when a color filter is used instead of a circular polarizer, it can still have both impact resistance and folding resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120813983A_ABST
    Figure CN120813983A_ABST
Patent Text Reader

Abstract

The present invention addresses the problem of providing: a display device having both visibility and folding resistance after a key test; an optical film; and a method for manufacturing the optical film. This display device has at least a light-emitting element and a color filter, and is characterized in that the display device has an optical film containing cellulose acetate and a filler of a metal oxide or a metal salt, the degree of substitution of acetyl groups in the cellulose acetate is within the range of 2.3-3.0, and the degree of substitution of acetyl groups in the cellulose acetate is within the range of 2.3-3.0. The metal oxide or metal salt filler has an aspect ratio in the range of 110-2000.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a display device, an optical film, and a manufacturing method of an optical film. More specifically, it relates to a display device or the like that has both visibility after a key test and folding resistance. BACKGROUND

[0002] Recently, development of a display device (flexible display) that can be folded and rolled is actively being conducted.

[0003] In a display device having a metal substrate inside, light is easily reflected on the surface of the metal substrate, and it is difficult to obtain sufficient visibility. Therefore, a technique of providing a circularly polarizing plate in a display device to improve visibility is known. However, in recent years, further thinning of a display device is required. A method of replacing the anti-reflection function of a circularly polarizing plate with other components without using a circularly polarizing plate is being studied.

[0004] As one of the methods, a method of replacing the function of a circularly polarizing plate with a color filter is known. By using this method, it is possible to further thin a display device. In contrast, a further thinned display device is easily subjected to an impact caused by a bending action or the like. Therefore, it is required to install a cover member that protects a display device to improve the impact resistance of the display device. Also, due to the thinning of the display device, the display device becomes easy to bend, and therefore, along with this, a higher folding resistance is required for the cover member.

[0005] In Patent Literature 1, a technique of an optical film containing needle-shaped particles having a specific refractive index is disclosed. In this technique, by containing needle-shaped particles having a specific refractive index in the optical film, the phase difference of the optical film is adjusted. However, in the case where this optical film is applied to a display device having a color filter, the impact resistance and the folding resistance of the display device are not sufficient.

[0006] PRIOR ART DOCUMENTS

[0007] PATENT LITERATURE

[0008] Patent Literature 1: Japanese Patent Application Laid-Open (JP A) No. 2008-281890 SUMMARY

[0009] The present application was made in view of the above problems and situations, and an object thereof is to provide a display device, an optical film, and a manufacturing method of an optical film that have both visibility after a key test and folding resistance.

[0010] The present inventors have studied the cause of the above problem and the like in order to solve the above problem, and as a result, have found that in a display device having at least a light emitting element and a color filter, the display device has an optical film containing cellulose acetate having a substitution degree of acetyl groups within a certain range and a filler of a metal oxide or a metal salt having an aspect ratio within a certain range, whereby the visibility after a key test and the folding resistance of the display device can be both satisfied, thereby completing the present invention.

[0011] That is, the above problem of the present invention can be solved by the following means.

[0012] 1. A display device having at least a light emitting element and a color filter, characterized by

[0013] the display device has an optical film,

[0014] the optical film contains cellulose acetate and a filler of a metal oxide or a metal salt,

[0015] the substitution degree of acetyl groups of the cellulose acetate is within a range of 2.3 to 3.0,

[0016] the aspect ratio of the filler of the metal oxide or the metal salt is within a range of 110 to 2000.

[0017] 2. The display device according to item 1, characterized in that

[0018] the arithmetic average of the indentation modulus of elasticity of the front and back surfaces of the optical film is within a range of 5.0 to 10.0 GPa.

[0019] 3. The display device according to item 1, characterized in that

[0020] in the optical film, the surface having a lower indentation modulus of elasticity is disposed on the light emitting element side.

[0021] 4. The display device according to item 1, characterized in that

[0022] the display device is disposed in the order of the optical film, the color filter, and the light emitting element.

[0023] 5. The display device according to item 1, characterized in that

[0024] the display device further has a glass layer between the optical film and the color filter.

[0025] 6. The display device according to item 1, characterized in that

[0026] the metal oxide is alumina.

[0027] 7. The display device according to claim 1, wherein

[0028] The content of the filler of the metal oxide or the metal salt is in the range of 1 to 30 mass% with respect to the total mass of the optical film.

[0029] 8. The display device according to claim 1, wherein

[0030] The light emitting element is an organic electroluminescence element,

[0031] The display device is flexible.

[0032] 9. The display device according to claim 8, wherein

[0033] The color filter has a function of preventing reflection of light incident from the outside.

[0034] 10. An optical film for a display device, comprising:

[0035] The optical film contains cellulose acetate and a filler of a metal oxide or a metal salt,

[0036] The degree of substitution of acetyl groups of the cellulose acetate is in the range of 2.3 to 3.0,

[0037] The filler of the metal oxide or the metal salt has an aspect ratio in the range of 110 to 2000, and

[0038] The display device has a color filter, and the color filter has a function of preventing reflection of light incident from the outside.

[0039] 11. A method for manufacturing an optical film according to claim 10, comprising:

[0040] a step of preparing a dope containing cellulose acetate and a filler of a metal oxide or a metal salt,

[0041] a step of casting the dope on a support to form a cast film,

[0042] a step of peeling the cast film from the support, and

[0043] a step of drying the cast film.

[0044] 12. The method for manufacturing an optical film according to claim 11, wherein

[0045] The cast film is dried by heating.

[0046] According to the above means of the present application, it is possible to provide a display device, an optical film, and a manufacturing method of an optical film, which have both visibility after a key test and folding resistance.

[0047] The effective expression mechanism or the action mechanism of the present application is not clear, but is presumed as follows.

[0048] As described above, in a display device having a color filter, an optical film applied to a cover member is particularly required to be provided with high impact resistance and folding resistance.

[0049] The optical film of the present application contains cellulose acetate in which the substitution degree of acetyl groups is within a certain range. In cellulose, by substituting a hydrogen atom of a hydroxyl group with a substituent (functional group or characteristic group) such as an acyl group, it is possible to change the reactivity of cellulose and the interaction acting between cellulose molecules. In the present application, the hydrogen atom of the hydroxyl group is esterified by being substituted with acetyl groups in a certain ratio. Thereby, it is considered that the network formed between the molecules of cellulose acetate has moderate flexibility and moderate rigidity. Also, it is considered that it is possible to moderately disperse the added filler.

[0050] In addition, the optical film of the present application contains a filler having an aspect ratio within a certain range. It is considered that by combining the above-described cellulose acetate and the filler, it is possible to maintain moderate flexibility and further impart moderate rigidity to the optical film. BRIEF DESCRIPTION OF DRAWINGS

[0051] Figure 1 is a cross-sectional view of a basic layer configuration of a display device.

[0052] Figure 2 is a cross-sectional view of a basic layer configuration of a display device in the case of having an adhesive layer.

[0053] Figure 3 is a cross-sectional view of a basic layer configuration of a display device in the case of having a glass layer.

[0054] Figure 4 is a cross-sectional view of a basic layer configuration of a display device in the case of having an adhesive layer and a glass layer.

[0055] Figure 5 is a schematic view showing one example of a method for producing thin film glass.

[0056] Figure 6 is a schematic view showing one example of a color display method preferably used in the present application.

[0057] Figure 7 is a schematic view showing one example of a color display method preferably used in the present application.

[0058] Figure 8is a schematic view of an example of a color display method preferably used in the present application.

[0059] Figure 9 is a schematic view of an example of a color display method preferably used in the present application.

[0060] Figure 10 is a schematic view of a color filter. DETAILED DESCRIPTION

[0061] The display device of the present application has at least a light emitting element and a color filter, characterized in that the display device has an optical film containing cellulose acetate and a filler of a metal oxide or a metal salt, the degree of substitution of acetyl groups of the cellulose acetate being in the range of 2.3 to 3.0, and the aspect ratio of the filler of the metal oxide or the metal salt being in the range of 110 to 2000.

[0062] This feature is a technical feature common to or corresponding to the following embodiments.

[0063] As an embodiment of the present application, from the viewpoint of combining the visibility after the key test (impact resistance) and the folding endurance, the arithmetic mean of the indentation modulus of elasticity of the front and back surfaces of the optical film is preferably in the range of 5.0 to 10.0 GPa.

[0064] As an embodiment of the present application, from the viewpoint of the visibility after the key test (impact resistance), in the optical film, the surface having a lower indentation modulus of elasticity is preferably disposed on the light emitting element side.

[0065] As an embodiment of the present application, from the viewpoint of the visibility after the key test (impact resistance), the above-mentioned optical film, the above-mentioned color filter, and the above-mentioned light emitting element are preferably disposed in the order.

[0066] As an embodiment of the present application, from the viewpoint of the visibility after the key test (impact resistance), the above-mentioned display device preferably further has a glass layer between the above-mentioned optical film and the above-mentioned color filter.

[0067] As an embodiment of the present application, from the viewpoint of being able to combine the mechanical strength and the visibility of the optical film, the above-mentioned metal oxide is preferably alumina.

[0068] As an embodiment of the present application, from the viewpoint of combining the visibility after the key test (impact resistance) and the folding endurance, the content of the filler of the metal oxide or the metal salt is preferably in the range of 1 to 30 mass% with respect to the total mass of the optical film.

[0069] As an embodiment of the present application, from the viewpoint of being able to significantly obtain an effect, the above-mentioned light emitting element is preferably an organic electroluminescent element, and the above-mentioned display device is flexible.

[0070] As an embodiment of the present application, from the viewpoint of thinning of the display device, it is preferable that the above-mentioned color filter has a function of preventing reflection of light incident from the outside.

[0071] The optical film of the present application is used for a display device, characterized in that the above-mentioned optical film contains cellulose acetate and a filler of metal oxide or metal salt, the substitution degree of acetyl group of the above-mentioned cellulose acetate is in the range of 2.3 to 3.0, the aspect ratio of the above-mentioned filler of metal oxide or metal salt is in the range of 110 to 2000, and the above-mentioned display device has a color filter, the above-mentioned color filter has a function of preventing reflection of light incident from the outside.

[0072] The manufacturing method of the optical film of the present application is a manufacturing method of the above-mentioned optical film, characterized by having: a step of preparing a dope containing the above-mentioned cellulose acetate and a filler of metal oxide or metal salt; a step of casting the above-mentioned dope on a support to form a cast film; a step of peeling the above-mentioned cast film from the above-mentioned support; and a step of drying the above-mentioned cast film.

[0073] As an embodiment of the present application, from the viewpoint of the unevenness of the filler, it is preferable that the above-mentioned cast film is dried by heating.

[0074] Hereinafter, the present application and its constituent elements, and the modes and manners for carrying out the present application will be explained in detail. It should be noted that, in the present application, "~" is used in the meaning that the numerical values written before and after it are included as lower limit values and upper limit values.

[0075] 1. Outline of display device

[0076] The display device of the present application has at least a light emitting element and a color filter, characterized in that the display device has an optical film, the above-mentioned optical film contains cellulose acetate and a filler of metal oxide or metal salt, the substitution degree of acetyl group of the above-mentioned cellulose acetate is in the range of 2.3 to 3.0, and the aspect ratio of the above-mentioned filler of metal oxide or metal salt is in the range of 110 to 2000.

[0077] It should be noted that, as needed, the display device can have other components or an adhesive layer for mounting each component.

[0078] Figure 1 and 2 shows a cross-sectional view of the basic layer configuration of the display device. The display device 10 has an optical film 1, a color filter 2, and a light emitting element 3 in this order. In addition, as shown in Figure 2 , an adhesive layer 4 can be provided between the optical film 1 and the color filter 2.

[0079] The member covering the display device can be composed of the optical film alone or can have other members as needed.

[0080] Figure 3 and 4 A cross-sectional view showing the basic layer configuration of the display device in the case of having a glass layer. The glass layer 5 can be disposed on the visible side with respect to the optical film 1 or on the side of the light emitting element 3. However, from the viewpoint that the optical film 1 also functions as a protective film for the glass layer 5, the glass layer 5 is preferably disposed on the side of the light emitting element with respect to the optical film 1. Further, as shown in Figure 4 An adhesive layer 4 can be provided between the optical film 1 and the glass layer 5.

[0081] By having the optical film of the present application, even if the thickness of the display device is thin, it is possible to have both the visibility after the key test (impact resistance) and the folding resistance. In particular, in the case where the light emitting element is an organic EL element and the function of the circularly polarizing plate is replaced with a color filter, the thickness of the display device is further thinned. Even in such a case, it is possible to have both the impact resistance and the folding resistance. Further, in the past, a thin film glass has been used as a cover member of the display device. However, even if the optical film of the present application is used as a cover member alone, that is, even if a thin film glass is not used, it is possible to have both the impact resistance and the folding resistance.

[0082] Hereinafter, the optical film, the glass layer, the color filter, and the light emitting element will be described respectively.

[0083] 2. Optical film

[0084] The optical film of the present application is an optical film for a display device, and contains cellulose acetate and a filler of a metal oxide or a metal salt, the degree of substitution of acetyl groups of the cellulose acetate is in the range of 2.3 to 3.0, the aspect ratio of the filler of the metal oxide or the metal salt is in the range of 110 to 2000, and it is preferably used together with a color filter having a function of preventing reflection of light incident from the outside.

[0085] (1) Configuration of optical film

[0086] The optical film of the present application contains cellulose acetate and a filler of a metal oxide or a metal salt. Note that other additives can also be contained as needed.

[0087] Hereinafter, the cellulose acetate, the filler of the metal oxide or the metal salt, and the additives will be described respectively.

[0088] (1.1) Cellulose acetate

[0089] The optical film contains cellulose acetate as a resin having a degree of substitution of acetyl groups in the range of 2.3 to 3.0. It is believed that the use of cellulose acetate facilitates the formation of a network between resin molecules, thereby imparting rigidity to the optical film.

[0090] Cellulose is a polymer composed of linear chains of β-glucose linked by β-1,4-glycosidic bonds. Cellulose esters are cellulose in which some or all of the hydrogen atoms at the 2nd, 3rd, and 6th hydroxyl groups (-OH) within a glucose unit have been replaced with acyl groups. Cellulose esters in which the acyl groups are acetyl groups are called "cellulose acetate."

[0091] (Degree of substitution of acetyl group)

[0092] The degree of acetyl substitution indicates the average number of acetyl groups in one glucose unit, that is, how many hydrogen atoms of the hydroxyl groups at the 2nd, 3rd, and 6th positions in one glucose unit are substituted with acetyl groups.

[0093] Therefore, the maximum value of the degree of substitution with acetyl groups is 3.0, which means that all the hydrogen atoms of the hydroxyl groups at the 2-, 3-, and 6-positions are substituted with acetyl groups.

[0094] The acetyl group may be substituted evenly at the 2-position, 3-position, and 6-position in one glucose unit, or may be substituted in a distributed manner.

[0095] The degree of substitution of acetyl groups can be determined by the method specified in ASTM-D817-96.

[0096] When the degree of substitution of acetyl groups in cellulose acetate is within the range of 2.3 to 3.0, appropriate rigidity can be imparted to the optical film and a suitable network can be formed between resin molecules.

[0097] From the viewpoint of obtaining desired optical properties, cellulose acetates having different degrees of substitution may be mixed and used. The mixing ratio of cellulose acetates having different degrees of substitution is not particularly limited.

[0098] From the viewpoint of mechanical strength, the number average molecular weight (Mn) of cellulose acetate is preferably 2×10 4 ~3×10 5 in the range of 2×10 4 ~1.2×10 5 In the range of 4×10 4 ~8×10 4 within the range.

[0099] From the viewpoint of mechanical strength, the weight average molecular weight (Mw) of cellulose acetate is preferably 2×10 4 ~1×10 6more preferably in the range of 2 x 10 4 ~ 1.2 x 10 5 more preferably in the range of 4 x 10 4 ~ 8 x 10 4 .

[0100] The number average molecular weight (Mn) and the weight average molecular weight (Mw) of the cellulose acetate can be measured by the following method.

[0101] < Gel Permeation Chromatography >

[0102] Solvent: dichloromethane

[0103] Column: Shodex K806, K805, K803G (manufactured by Showa Denko K.K.) 3 were connected and used

[0104] Column temperature: 25°C

[0105] Sample concentration: 0.1 mass%

[0106] Detector: RI Model 504 (manufactured by GL Sciences Inc.)

[0107] Pump: L6000 (manufactured by Hitachi, Ltd.)

[0108] Flow rate: 1.0 mL / min

[0109] Calibration curve: A calibration curve was prepared using 13 samples of standard polystyrene STK standard polystyrene (manufactured by Tosoh Corporation) having a Mw in the range of 500 to 2800000. Preferably, the 13 samples were used at approximately equal intervals.

[0110] The cellulose acetate can be synthesized by a publicly known method.

[0111] As the raw material cellulose of the cellulose acetate, there is no particular limitation, and examples include cotton linter, wood pulp, kenaf, and the like. The raw material cellulose, acetic acid, acetic anhydride, and a catalyst (sulfuric acid or the like) are mixed, and the cellulose is esterified. Note that the reaction is performed until triester of the cellulose is formed. In the triester, all of the hydrogen atoms of the three hydroxyl groups in one glucose unit are substituted with acetyl groups.

[0112] Next, the cellulose acetate having a desired degree of substitution of acetyl groups is obtained by hydrolyzing the triester of the cellulose.

[0113] Then, the cellulose acetate is finally obtained through processes such as filtration, precipitation, water washing, dehydration, drying, and the like. Specifically, the synthesis can be performed by referring to the method described in Japanese Patent Application Publication No. 10-45804.

[0114] (1.2) Metal oxide or metal salt filler

[0115] The optical film contains a metal oxide or metal salt filler having an aspect ratio in the range of 110 to 2000. By using this filler, the mechanical strength of the optical film can be improved. Specifically, the indentation elastic modulus of the optical film can be improved. In addition, by using this filler, sufficient visibility (transparency) of the optical film can be obtained, and thus sufficient visibility can be obtained even when used in a display device.

[0116] The metal oxide or metal salt filler is a needle-like particle of a metal oxide or metal salt, and preferably has a surface modified. In the present specification, the "metal oxide or metal salt filler" is also referred to simply as "filler".

[0117] The content of the filler is preferably in the range of 1 to 30% by mass, and more preferably in the range of 1 to 10% by mass, with respect to the total mass of the optical film.

[0118] (1.2.1) Material of the metal oxide or metal salt filler

[0119] The metal oxide is not particularly limited. As the metal oxide, for example, aluminium oxide, silica, magnesium oxide, zinc oxide, lead oxide, boehmite, pseudoboehmite, tantalum oxide, indium oxide, bismuth oxide, yttrium oxide, cobalt oxide, copper oxide, manganese oxide, selenium oxide, iron oxide, zirconia, germanium oxide, tin oxide, titanium oxide, niobium oxide, molybdenum oxide, and the like can be given. These can be used singly as one kind, or two or more kinds can be used in combination.

[0120] The metal salt is not particularly limited. As the metal salt, for example, strontium carbonate, calcium carbonate, magnesium carbonate, cobalt carbonate, manganese carbonate, barium carbonate, potassium carbonate, and the like can be given. These can be used singly as one kind, or two or more kinds can be used in combination.

[0121] Among them, from the viewpoint of being able to have both the mechanical strength and the visibility of the optical film, the metal oxide is preferably aluminium oxide, and the metal salt is preferably strontium carbonate.

[0122] (1.2.2) Aspect ratio of the metal oxide or metal salt filler

[0123] The aspect ratio of the metal oxide or metal salt filler of the present application is in the range of 110 to 2000. By being in the above range, the mechanical strength of the optical film can be improved. Specifically, the indentation elastic modulus of the optical film can be improved.

[0124] In the present application, the aspect ratio of the filler and the filler precursor described later can be measured by the following method.

[0125] The cross section of the optical film was directly photographed by a scanning electron microscope (SEM). Then, at least 100 fillers were randomly selected from the obtained image (SEM image). The length diameter (x) and the short diameter (y) of each filler were measured, respectively. The value (x / y) obtained by dividing the length diameter (x) by the short diameter (y) was calculated, and the average value thereof was taken as the "length diameter ratio".

[0126] In the case where a circumscribed rectangle (circumscribed rectangle) is drawn around each filler, the length of the short side is taken as the short diameter, and the length of the long side is taken as the length diameter. Generally, the length diameter (x) and the short diameter (y) of the filler correspond to the average length and the average diameter, respectively.

[0127] From the viewpoint of being able to achieve both the mechanical strength and the visibility of the optical film, the length diameter ratio of the filler is preferably in the range of 200 to 1500, and more preferably in the range of 500 to 1200.

[0128] The average diameter of the filler is not particularly limited, but is preferably in the range of 1 to 10 nm. By making the average diameter 1 nm or more, it is possible to impart sufficient mechanical strength to the optical film. In addition, by making the diameter 10 nm or less, it is possible to suppress the decrease in the visibility of the optical film. The average diameter of the filler is more preferably in the range of 4 to 8 nm. Note that this average diameter corresponds to the short diameter (y) of the "length diameter ratio" described above.

[0129] (1.2.3) Surface modifier

[0130] From the viewpoint of the dispersibility of the filler in the optical film, it is preferable that the filler is surface-modified. It is preferable that the surface is provided with a sulfonic acid group (-SO3H), a carboxyl group (-COOH), or a phosphate group (-P(=O)(OH) 3-n ) by surface modification. Note that n of the phosphate group is 1 or 2.

[0131] Hereinafter, preferable modes of the surface modifier will be described, but the present application is not limited thereto.

[0132] The compound having a sulfonic acid group (-SO3H) is not particularly limited, and examples thereof include alkyl sulfonic acids such as methane sulfonic acid and ethane sulfonic acid; aromatic sulfonic acids such as benzene sulfonic acid, p-toluene sulfonic acid, styrene sulfonic acid, and dodecyl benzene sulfonic acid; and the like. In addition, examples thereof include alkali metal salts and ammonium salts of these sulfonic acids, esters of these sulfonic acids with lower alcohols, and the like.

[0133] The compound having a carboxyl group (-COOH) is not particularly limited, and examples thereof include monocarboxylic acids such as formic acid, acetic acid, and propionic acid; dicarboxylic acids such as oxalic acid, fumaric acid, and maleic acid; hydroxycarboxylic acids such as lactic acid, malic acid, and citric acid; aromatic carboxylic acids such as benzoic acid and salicylic acid; salts thereof; and the like.

[0134] The compound having a phosphate group (-P(=O)(OH) 3-n The compound having a phosphate group (-P(=O)(OH)

[0135] The surface modifier preferably has an aromatic group.

[0136] As the surface modifier having an aromatic group, for example, aromatic sulfonic acids such as benzenesulfonic acid, p-toluenesulfonic acid, styrenesulfonic acid, and dodecylbenzenesulfonic acid can be given. In addition, alkali metal salts and ammonium salts of these aromatic sulfonic acids, esters of these aromatic sulfonic acids with lower alcohols, and the like can be given. Also, aromatic carboxylic acids such as benzoic acid and salicylic acid, or salts thereof can be given.

[0137] (1.2.4) Method for producing the filler of the metal oxide or the metal salt

[0138] (1.2.4.1) Method for producing the filler of the metal oxide

[0139] The method for producing the filler of the metal oxide is not particularly limited, and can be produced by the same method as the known method described in Japanese Patent Application Publication No. 2016-44114, or the like.

[0140] For example, a method in which a metal oxide raw material is hydrolyzed in an aqueous acid solution to form a hydrated oxide, the generated alcohol is distilled off, and then, the metal oxide filler precursor (aqueous metal oxide sol) is obtained by peptization, and then, the metal oxide filler precursor is treated with a surface modifier (dehydration treatment) can be given.

[0141] Hereinafter, the above method will be described in detail. Note that the present application is not limited to this.

[0142] First, a metal oxide raw material is hydrolyzed in an aqueous acid solution to obtain a hydrated oxide. Here, the metal oxide raw material is not particularly limited. The metal oxide raw material can use an alkoxide, an oligomer, acetylacetone, or the like of the metal constituting the above metal oxide.

[0143] Examples of the metal oxide raw material include metal alkoxides such as ethyl aluminum ethoxide, isopropyl aluminum ethoxide, n-butyl aluminum diethoxide, sec-butyl aluminum diethoxide, tetraethoxysilane, tetrapropoxysilane, tetraisopropoxysilane, tetra-sec-butoxysilane, tetra-n-butoxysilane, tetraisopropoxytitanium, tetra-n-butoxytitanium, tetra-tert-butoxytitanium, tetra-n-butoxyzirconium, and zirconium alkoxide; and cyclic aluminum oligomers, diisopropoxy(ethyl acetoacetate)aluminum, and tri(ethyl acetoacetate)aluminum.

[0144] The metal oxide raw material can be used singly or in combination of two or more. Of the metal oxide raw materials, an alcoholate of aluminum, silicon, or zirconium is preferably used. Further, an alcoholate of aluminum, silicon, or zirconium having a carbon number of 2 to 4 is more preferably used.

[0145] The acid used for the hydrolysis is not particularly limited, and examples thereof include hydrochloric acid, nitric acid, formic acid, acetic acid, propionic acid, and butyric acid. Of these, formic acid, acetic acid, propionic acid, or butyric acid is preferably used from the viewpoint of ease of handling, and acetic acid is more preferably used.

[0146] The amount of the acid used is not particularly limited, and for example, it is preferably in the range of 0.2 to 2.0 mol, and more preferably in the range of 0.3 to 1.8 mol, relative to 1 mol of the metal oxide raw material. By being in the above range, the metal oxide raw material can be efficiently hydrolyzed, and a filler having a desired shape (aspect ratio, diameter) can be produced. The acid can be used in the form of an aqueous solution. The concentration of the acid in the aqueous solution is not particularly limited, and for example, it is preferably in the range of 10 to 50 mass%, and more preferably in the range of 15 to 30 mass%.

[0147] The conditions for the hydrolysis are not particularly limited as long as the metal oxide raw material can be hydrolyzed, and can be appropriately selected depending on the kind of the metal oxide raw material, the amount of the acid used, and the like. For example, the hydrolysis temperature is preferably in the range of 50 to 100°C. Further, the hydrolysis time is preferably in the range of 10 minutes to 3 hours. If the conditions are such, the metal oxide raw material can be efficiently hydrolyzed, and a filler having a desired shape (aspect ratio, diameter) can be produced.

[0148] The obtained hydrated oxide is peptized while distilling off the generated alcohol, and a water-based metal oxide sol is obtained. Here, the hydrated oxide is in the form of a solution (for example, an aqueous solution). The concentration of the hydrated oxide (solid content concentration) at this time is not particularly limited, and for example, it is preferably in the range of 2 to 15 mass%, and more preferably in the range of 3 to 10 mass%. By being in the above range, the hydrated oxide can be efficiently peptized.

[0149] The peptization conditions are not particularly limited as long as the conditions are capable of peptizing the hydrated oxide. For example, the peptization temperature is preferably in the range of 100 to 200°C, and more preferably in the range of 110 to 180°C. The peptization time is preferably in the range of 1 to 20 hours, and more preferably in the range of 2 to 15 hours. By being in the above ranges, the hydrated oxide can be efficiently peptized, and the filler having the desired shape (aspect ratio, diameter) can be produced.

[0150] By the above method, the precursor of the metal oxide filler (aqueous metal oxide sol) is obtained. Here, the shape of the precursor of the metal oxide filler is not particularly limited. However, it is substantially the same shape as the metal oxide filler as the final product. That is, the average diameter of the precursor of the metal oxide filler is preferably in the range of 1 to 10 nm, and more preferably in the range of 4 to 8 nm. The aspect ratio of the precursor of the metal oxide filler is in the range of 110 to 2000, and preferably in the range of 120 to 1000.

[0151] Next, the precursor of the metal oxide filler (aqueous metal oxide sol) is treated with a surface modifier. Specifically, an organic solvent and a surface modifier are added to the precursor of the metal oxide filler (aqueous metal oxide sol) obtained above, and mixed. Then, solvent replacement is performed. The method of solvent replacement is not particularly limited, and for example, a method using an ultrafiltration membrane, a dehydration method using the difference in boiling point between water and the organic solvent, or the like can be used. Note that the surface modifier is the same as the surface modifier described above.

[0152] The amount of the surface modifier used is not particularly limited as long as the amount is capable of surface-modifying the precursor of the metal oxide filler. Note that "surface-modifying the precursor of the metal oxide filler" means disposing the surface modifier on the surface of the metal oxide filler. Specifically, the amount of the surface modifier used is preferably in the range of 1 to 100% by mass, and more preferably in the range of 10 to 20% by mass, with respect to the precursor of the metal oxide filler. By being in the above ranges, the precursor of the metal oxide filler can be surface-modified to the desired extent. That is, the surface modifier can be disposed on the surface of the metal oxide filler to the desired extent.

[0153] The organic solvent that can be used for the surface modification is not particularly limited, and can be appropriately selected depending on the kind of the precursor of the metal oxide filler and the surface modifier. Specifically, the organic solvent can be benzene, toluene, xylene, ethylbenzene, diethylbenzene, mesitylene, triethylbenzene, cyclohexane, cyclohexene, decalin, dipentene, pentane, hexane, heptane, octane, nonane, decane, ethylcyclohexane, methylcyclohexane, p-menthane, dipropyl ether, dibutyl ether, anisole, butyl acetate, amyl acetate, methyl isobutyl ketone, or the like.

[0154] These solvents can be used singly or in combination of two or more.

[0155] The amount of the organic solvent used is not particularly limited. The amount of the organic solvent used is preferably selected so that the total concentration of the precursor of the filler of the metal oxide and the surface modifier becomes, for example, in the range of 1 to 20% by mass, preferably in the range of 2 to 10% by mass.

[0156] The surface modification (dehydration treatment) conditions are not particularly limited as long as the precursor of the filler of the metal oxide can be surface-modified to the desired extent. If such conditions are used, the precursor of the filler of the metal oxide can be treated with the surface modifier, and a filler having a desired shape (aspect ratio, diameter) can be produced.

[0157] (1.2.4.2) Method for producing the filler of the metal salt

[0158] The method for producing the filler of the metal salt is not particularly limited, and can be produced by the same method as the known method.

[0159] Hereinafter, as an example, the method for producing the filler of strontium carbonate will be described. It should be noted that the present application is not limited to this.

[0160] The needle-like strontium carbonate particles can be produced, for example, by heating fine spherical strontium carbonate particles in water to grow the crystal grains. In addition, the spherical strontium carbonate particles can be produced, for example, by a method of carbonating strontium hydroxide.

[0161] Specifically, while stirring an aqueous solution or an aqueous suspension of strontium hydroxide, carbon dioxide gas is introduced to the aqueous solution or the aqueous suspension in the presence of an organic acid. The concentration of strontium hydroxide in the aqueous solution or the aqueous suspension is preferably in the range of 1 to 20% by mass, more preferably in the range of 2 to 15% by mass, and further preferably in the range of 3 to 8% by mass.

[0162] The organic acid preferably has at least one hydroxyl group and at least one carboxyl group each, and a total of at least three. As the organic acid, for example, tartaric acid, malic acid, and gluconic acid can be given. The amount of the organic acid used is preferably in the range of 0.1 to 20% by mass, more preferably in the range of 1 to 10% by mass, with respect to the total mass of strontium hydroxide.

[0163] The flow rate of the carbon dioxide gas is preferably in the range of 0.5 to 200 mL / minute, more preferably in the range of 0.5 to 100 mL / minute, with respect to 1 g of strontium hydroxide. It should be noted that the spherical strontium carbonate particles can be produced by the method described in International Publication No. 2011 / 052680.

[0164] As a method of surface-modifying the needle-like strontium carbonate particles, the same method as that of surface-modifying the precursor of the metal oxide filler described above can be used.

[0165] (1.3) Additives

[0166] The optical film of the present application can further contain other additives. As the other additives, there is no particular limitation, and the additives used in the past can be used. For example, plasticizers, matting agents, ultraviolet absorbers, antioxidants, phase difference control agents, peeling promoters, and the like can be mentioned. In addition to these additives, additives generally used for optical films can also be used as needed.

[0167] (1.3.1) Plasticizers

[0168] By making the optical film contain a plasticizer, the flexibility and processability of the optical film can be improved. As the plasticizer, for example, a polyester can be used. The polyester can be obtained by polymerizing a dicarboxylic acid with a diol. In addition, it is preferable that 70% or more of the dicarboxylic acid structural units (structural units from a dicarboxylic acid) come from an aromatic dicarboxylic acid, and 70% or more of the diol structural units (structural units from a diol) come from an aliphatic diol.

[0169] The proportion of the structural units from the aromatic dicarboxylic acid is preferably 70% or more, more preferably 80% or more, and further more preferably 90% or more. The proportion of the structural units from the aliphatic diol is preferably 70% or more, more preferably 80% or more, and further more preferably 90% or more. The polyester can be used singly or in combination of two or more kinds.

[0170] As the aromatic dicarboxylic acid, for example, terephthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid and the like, 4,4'-biphenyl dicarboxylic acid, 3,4'-biphenyl dicarboxylic acid and the like, and ester-forming derivatives thereof can be mentioned.

[0171] Within a range that does not impair the object of the present application, for the polyester, aliphatic dicarboxylic acids such as adipic acid, azelaic acid, sebacic acid, and the like; monocarboxylic acids such as benzoic acid, propionic acid, butyric acid, and the like can be used.

[0172] As the aliphatic diol, for example, ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,4-cyclohexane dimethanol, 1,6-hexanediol and the like, and ester-forming derivatives thereof can be mentioned.

[0173] Within a range that does not impair the object of the present application, for the polyester, monohydric alcohols such as butanol, hexanol, octanol and the like; polyhydric alcohols such as trimethylolpropane, glycerol, pentaerythritol and the like can also be used.

[0174] As a method for synthesizing the polyester, a direct esterification method and a transesterification method, which are known methods, can be used. As a polycondensation catalyst used in the synthesis of the polyester, antimony compounds such as antimony trioxide and antimony pentoxide; germanium compounds such as germanium oxide; titanium compounds such as titanium acetate; aluminum compounds such as aluminum chloride; and the like can be given. However, the polycondensation catalyst is not limited to these.

[0175] As the preferred polyester, polyethylene terephthalate, polyethylene terephthalate-isophthalate copolymer, poly(l,4-cyclohexanedimethylene terephthalate) glycol copolymer, poly-2,6-naphthalene dicarboxylic acid glycol ester, poly-2,6-naphthalene dicarboxylic acid-terephthalic acid glycol copolymer, poly(terephthalic acid-4,4'-biphenyldicarboxylic acid) glycol ester, poly-1,3-propanediol terephthalate, polybutylene terephthalate, polybutylene-2,6-naphthalene dicarboxylic acid glycol ester, and the like can be given.

[0176] As the more preferred polyester resin, polyethylene terephthalate, polyethylene terephthalate-isophthalate copolymer, poly(l,4-cyclohexanedimethylene terephthalate) glycol copolymer, polybutylene terephthalate, and poly-2,6-naphthalene dicarboxylic acid glycol ester can be given.

[0177] (1.3.2) Matting agent

[0178] By containing a matting agent in the optical film, the handleability can be improved. As the matting agent, for example, inorganic microparticles such as silicon dioxide, titanium dioxide, aluminum oxide, zirconium oxide, calcium carbonate, kaolin, talc, baked calcium silicate, hydrated calcium silicate, aluminum silicate, magnesium silicate, calcium phosphate, and the like; and crosslinked polymers, and the like can be given. Among these, from the viewpoint of reducing the haze of the film and the like, the matting agent is preferably silicon dioxide. These matting agents can be used singly or in combination of two or more.

[0179] In the case where the matting agent is microparticles, the primary average particle diameter of the microparticles is not particularly limited. The primary average particle diameter is preferably in the range of 1 to 20 nm, more preferably in the range of 5 to 16 nm, and further preferably in the range of 5 to 12 nm.

[0180] In addition, it is preferable that the microparticles are contained in the optical film in a state of forming secondary particles. The secondary average particle diameter is preferably in the range of 0.1 to 5 μm, more preferably in the range of 0.1 to 2 μm, and further preferably in the range of 0.2 to 0.6 μm. Thereby, it is possible to form a concave-convex having a height in the range of 0.1 to 1.0 μm on the surface of the optical film, and it is possible to impart an appropriate smoothness to the surface of the optical film. The measurement of the primary average particle diameter of the microparticles is performed by observing the particles with a transmission electron microscope at a magnification in the range of 500,000 to 2,000,000. 100 particles are observed, the particle diameters are measured, and the average value thereof is used as the primary average particle diameter.

[0181] (1.3.3) Ultraviolet absorber

[0182] By containing the optical film with an ultraviolet absorber, light resistance can be improved. The purpose of the ultraviolet absorber is to improve light resistance by absorbing ultraviolet rays having a wavelength of 400 nm or less. The ultraviolet absorber is particularly preferably one having a transmittance at a wavelength of 370 nm in the range of 0.1 to 30%, more preferably in the range of 1 to 20%, and further preferably in the range of 2 to 10%.

[0183] As the ultraviolet absorber, for example, benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, triazine-based ultraviolet absorbers, and the like can be given. Among them, the ultraviolet absorber is preferably a benzotriazole-based ultraviolet absorber or a benzophenone-based ultraviolet absorber.

[0184] As the benzotriazole-based ultraviolet absorber and the benzophenone-based ultraviolet absorber, for example, 5-chloro-2-(3,5-di-sec-butyl-2-hydroxyphenyl)-2H-benzotriazole, (2-2H-benzotriazol-2-yl)-6-(linear and branched dodecyl)-4-methylphenol, 2-hydroxy-4-benzyloxybenzophenone, 2,4-benzyloxybenzophenone, and the like can be given.

[0185] In addition, "Tinuvin (registered trademark) 109", "Tinuvin (registered trademark) 171", "Tinuvin (registered trademark) 234", "Tinuvin (registered trademark) 326", "Tinuvin (registered trademark) 327", "Tinuvin (registered trademark) 328", "Tinuvin (registered trademark) 928", and the like of the "Tinuvin (registered trademark)" series can be given. These are all commercially available products manufactured by BASF Japan Ltd., and can be preferably used. Among them, the "Tinuvin (registered trademark)" series is preferably an ultraviolet absorber having no halogen group.

[0186] In addition to these, a discotic compound such as a compound having a 1,3,5-triazine ring is also preferably used as the ultraviolet absorber. For example, "Tinuvin (registered trademark) 400", "Tinuvin (registered trademark) 405" (both manufactured by BASF Japan Ltd.), "LA-46" (manufactured by ADEKA Corporation), and the like can be given.

[0187] These ultraviolet absorbers can be used singly or in combination of two or more.

[0188] As the ultraviolet absorber, a high-molecular ultraviolet absorber can also be preferably used. It is particularly preferable to use a polymer-type ultraviolet absorber described in Japanese Patent Application Laid-Open No. 6-148430. Further, the ultraviolet absorber is preferably one having no halogen group.

[0189] As the method of adding the ultraviolet absorber, there can be mentioned a method of dissolving the ultraviolet absorber in a solvent and then adding the solution to the paste, or a method of directly adding the ultraviolet absorber in the preparation of the paste. As the solvent, there can be mentioned methanol, ethanol, butanol and the like alcohols, dichloromethane, methyl acetate, acetone, dioxolane and the like organic solvents, or a mixed solvent thereof. The ultraviolet absorber which is not dissolved in the organic solvent like the inorganic powder can be dispersed in the organic solvent by using a dissolver, a sand mill, and then added to the paste.

[0190] The content of the ultraviolet absorber is preferably appropriately selected depending on the kind of the ultraviolet absorber, the use conditions and the like. The content of the ultraviolet absorber is preferably in the range of 0.5 to 10% by mass, further preferably in the range of 0.6 to 4% by mass, relative to the total mass of the cellulose acetate.

[0191] (1.3.4) Antioxidant

[0192] The optical film contains an antioxidant, whereby deterioration under a high-temperature high-humidity environment can be prevented.

[0193] As the antioxidant, a hindered phenol-based compound is preferably used. As the hindered phenol-based compound, there can be mentioned, for example, 2,6-di-tert-butyl-p-cresol, pentaerythritol-tetra-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, triethylene glycol-bis-3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate, 1,6-hexanediol-bis-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2,4-bis-(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butyl anilino)-1,3,5-triazine, 2,2-thio-bis-ethylene glycol-bis-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, N,N'-hexamethylene-bis-3,5-di-tert-butyl-4-hydroxy-hydrocinnamamide, 1,3,5-trimethyl-2,4,6-tris-3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tris-3,5-di-tert-butyl-4-hydroxybenzyl)-isocyanurate, and the like.

[0194] Among them, the hindered phenol-based compound is preferably 2,6-di-tert-butyl-p-cresol, pentaerythritol-tetra [3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] or triethylene glycol-bis [3-(3-tert-butyl-5-methyl-4-hydroxyphenyl) propionate].

[0195] In addition, for example, a hydrazine-based metal deactivator such as N,N'-bis [3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyloxy] hydrazine and a phosphorus-based processing stabilizer such as tris(2,4-di-tert-butylphenyl) phosphite can be used in combination. These antioxidants can be used singly or in combination of two or more.

[0196] The content of the antioxidant is not particularly limited, and is preferably in the range of 1 mass ppm to 1.0 mass% and more preferably in the range of 10 to 1000 mass ppm, relative to the total mass of the cellulose acetate.

[0197] (1.3.5) Phase difference controlling agent

[0198] By containing the phase difference controlling agent in the optical film, it is possible to improve the display quality of the display device. As the phase difference controlling agent, there can be mentioned an aromatic compound having two or more aromatic rings as described in European Patent No. 911656A2, a rod-shaped compound as described in Japanese Patent Application Publication No. 2006-2025, or the like. In addition, two or more aromatic compounds can be used in combination.

[0199] The aromatic ring of the aromatic compound preferably contains an aromatic heterocycle in addition to an aromatic hydrocarbon ring. The aromatic heterocycle is generally an unsaturated heterocycle. Among them, the aromatic compound containing the aromatic heterocycle is preferably a 1,3,5-triazine ring as described in Japanese Patent Application Publication No. 2006-2026.

[0200] The content of the phase difference controlling agent is preferably in the range of 0.5 to 20 mass% and more preferably in the range of 1 to 10 mass%, relative to the total mass of the cellulose acetate.

[0201] (1.3.6) Peeling promoter

[0202] By containing the peeling promoter in the optical film, it is possible to reduce the peeling resistance of the optical film. The peeling promoter preferably uses a surfactant.

[0203] As the peeling promoter, there can be mentioned a phosphate ester-based surfactant, a carboxylic acid or carboxylic acid salt-based surfactant, a sulfonic acid or sulfonic acid salt-based surfactant, a sulfate ester-based surfactant, or the like.

[0204] In addition, as the peeling promoter, among the above-mentioned surfactants, a fluorine-based surfactant in which a part of hydrogen atoms bonded to a hydrocarbon chain is substituted with a fluorine atom can be mentioned. The peeling promoter is exemplified in the following.

[0205] RZ-1: C8H 17 O-P(=O)-(OH)2

[0206] RZ-2: C 12 H 25 O-P(=O)-(OK)2

[0207] RZ-3: C 12 H 25 OCH2CH2O-P(=O)-(OK)2

[0208] RZ-4: C 15 H 31 (OCH2CH2)5O-P(=O)-(OK)2

[0209] RZ-5: {C 12 H 25 O(CH2CH2O)5}2-P(=O)-OH

[0210] RZ-6: {C 18 H 35 (OCH2CH2)8O}2-P(=O)-ONH4

[0211] RZ-7: (t-C4H9)3-C6H2-OCH2CH2O-P(=O)-(OK)2

[0212] RZ-8: (iso-C9H 19 -C6H4-O-(CH2CH2O)5-P(=O)-(OK)(OH) 12 H 25 SO3Na

[0213] RZ-10: C 12 H 25 OSO3Na

[0214] RZ-11: C 17 H 33 COOH

[0215] RZ-12: C 17 H 33 COOH-N(CH2CH2OH)3

[0216] RZ-13: iso-C8H 17-C6H4-O-(CH2CH2O)3-(CH2)2SO3Na

[0217] RZ-14: (iso-C9H 19 )2-C6H3-O-(CH2CH2O)3-(CH2)4SO3Na

[0218] RZ-15: triisopropyl naphthalene sulfonic acid sodium salt

[0219] RZ-16: tri-tert-butyl naphthalene sulfonic acid sodium salt

[0220] RZ-17: C 17 H 33 CON(CH3)CH2CH2SO3Na

[0221] RZ-18: C 12 H 25 -C6H4SO3-NH4

[0222] The content of the release accelerator is preferably in the range of 0.05 to 5% by mass, more preferably in the range of 0.1 to 2% by mass, and further preferably in the range of 0.1 to 0.5% by mass, relative to the total mass of the cellulose acetate.

[0223] (2) Physical properties of the optical film

[0224] (2.1) Indentation elastic modulus

[0225] The optical film of the present application preferably has an arithmetic mean of the indentation elastic modulus of the front and back surfaces of the optical film in the range of 5.0 to 10.0 GPa. By being in the above range, the optical film has sufficient mechanical strength. Also, by being installed in a display device, the display device can be protected from impacts from the outside, and the color filter, light emitting element, and the like inside the display device can be protected. Particularly, in the case where the color filter is used instead of the function of the circularly polarizing plate, by having the indentation elastic modulus in the above range, the display device has sufficient impact resistance and can be further thinned.

[0226] The indentation elastic modulus of the optical film can be measured by the following method.

[0227] The optical film is cut into about 2 cm square, and the opposite surface of the measurement surface is fixed with an adhesive on a glass plate having a thickness of about 1 mm. Then, conditioning is performed by leaving it in an atmosphere of 23°C, 50% RH for 12 hours.

[0228] The indentation elastic modulus is measured for the sample using an indentation hardness tester in accordance with ISO 14577-1 Annex A. As the indentation hardness tester, for example, a dynamic ultra-micro hardness tester "DUH-211S" (manufactured by Shimadzu Corporation) is used. The test force is set to 12 mN.

[0229] Note that the indentation modulus is measured at 10 equal parts in the width direction of the optical film. However, both ends of the optical film are not included. Among the 9 measured values obtained, the arithmetic mean of 7 values excluding the maximum and minimum values is calculated.

[0230] In the present application, "the surface and the back surface of the optical film" refer to the two faces having the largest areas, which are in parallel relationship. Of these, one face is set as the surface and the other face is set as the back surface. Note that either of the two faces having the largest areas can be set as the surface.

[0231] In the present application, "the arithmetic mean of the indentation modulus of the surface and the back surface of the optical film" refers to, first, the indentation modulus is separately calculated for the surface and the back surface of the optical film by the above method, and then the values of the obtained indentation modulus are added and further divided by 2.

[0232] The arithmetic mean of the indentation modulus of the surface and the back surface of the optical film is preferably in the range of 5.0 to 10.0 GPa, more preferably in the range of 6.0 to 9.0 GPa, and further preferably in the range of 6.0 to 8.0 GPa.

[0233] (2.2) Bias of the filler in the thickness direction of the optical film

[0234] The number of the filler per unit area of the present application gradually increases or gradually decreases from the surface to the back surface, that is, it is preferably biased. In other words, it is preferable that the presence density of the filler continuously changes in the thickness direction of the optical film. The "presence density" here refers to the content of the filler per unit area of the cross section of the optical film.

[0235] Note that the continuous change can be any of a linearly increasing manner, a curvilinearly increasing manner, and a manner of increasing in multiple stages.

[0236] In the thickness direction of the optical film, whether the filler is biased or not can be confirmed by the following method. In addition, from the viewpoint that the hardness can be imparted using the filler, if the values of the respective indentation modulus of the surface and the back surface of the optical film are different, it can be confirmed that the filler is biased.

[0237] The optical film is cut by a microtome to obtain a cut surface perpendicular to the surface or the back surface of the optical film. The obtained cut surface of the optical film is observed by TEM. The observation conditions are, for example, acceleration voltage (electron energy irradiated on the sample): 30 kV, action distance (distance between the lens and the sample): 8.6 mm x magnification: 3.00 k. The observation area is an area including the entire region in the thickness direction of the optical film.

[0238] The obtained TEM image is subjected to brightness gradient removal using image processing software of "NiVision" (manufactured by National Instruments). Then, an opening operation is performed to detect the contrast difference between the cellulose acetate and the filler. The distribution state of the filler can be specified.

[0239] The obtained image after processing is observed. The number of fillers per unit area in a region Al from the surface to a region of 20% or less of the thickness of the optical film is calculated. The number of fillers per unit area in a region A2 from the back surface to a region of 20% or less of the thickness of the optical film is calculated. The number of fillers per unit area in a region B (from the surface of the optical film to a region of more than 20% and less than 80% of the thickness of the optical film) sandwiched by these two regions is calculated.

[0240] It is preferable that the number of fillers per unit area increases or decreases in the order of regions Al, B, A2.

[0241] The method of making the fillers thus biased is not particularly limited. For example, when the film is formed using a solution casting method, the diffusion behavior of the fillers in the casting dope or in the film-shaped article after peeling can be adjusted. In addition, the fillers can be biased by the difference in specific gravity between the cellulose acetate and the fillers. In addition to this, the fillers can be biased by the affinity of the casting dope to the support at the time of casting. Thus, by appropriately selecting the degree of substitution of the cellulose acetate, the type of the fillers, the type of the support at the time of casting, and the like, the degree of biasing of the fillers can be adjusted.

[0242] The diffusion behavior of the fillers can be adjusted, for example, by the drying conditions of the casting dope or the film-shaped article, specifically, by the amount of residual solvent at the time of peeling, the drying temperature, the time, and the like. In addition, the diffusion behavior of the fillers can be adjusted by the type of the cellulose acetate, the affinity of the fillers to the solvent, and the like.

[0243] In order to make the fillers more biased toward the surface or the back surface of the optical film (regions Al, A2), it is preferable to increase the amount of residual solvent of the film-shaped article at the time of peeling as described later, and to lower the drying temperature of the film-shaped article after peeling to Tg or less.

[0244] (3) Method for producing an optical film

[0245] The method for producing an optical film of the present application preferably has a step of preparing a casting dope containing the above-described cellulose acetate and fillers of metal oxides or metal salts; a step of casting the above-described casting dope on a support to form a cast film; a step of peeling the above-described cast film from the above-described support; and a step of drying the above-described cast film.

[0246] The method for producing the optical film of the present application is not particularly limited, but from the viewpoint of obtaining the desired optical film, it is preferable to produce it by a solution casting method.

[0247] In the solution casting method, after a dope containing a resin, a solvent, and optionally other components is prepared, the dope is applied to a substrate, and then dried to obtain an optical film.

[0248] Next, the method for producing an optical film by a solution casting method will be described.

[0249] (3.1) Step of preparing a dope

[0250] The step of preparing a dope will be described. When the concentration of cellulose acetate in the dope is relatively high, it is preferable because it reduces the drying load after casting on a metal support. However, if the concentration of cellulose acetate is too high, the load during filtration increases, and the filtration precision deteriorates. As a concentration that balances these, it is preferable to be in the range of 10 to 35 mass%, and more preferably in the range of 15 to 25 mass%.

[0251] The solvent used in the dope can be used alone or in combination with two or more. From the viewpoint of production efficiency, it is preferable to use a good solvent for cellulose acetate in combination with a poor solvent. As a good solvent, for example, dichloromethane or methyl acetate can be given. As a poor solvent, for example, methanol, ethanol, n-butanol, cyclohexane, cyclohexanone, and the like can be given.

[0252] In the dope, it is preferable to contain water in the range of 0.01 to 2 mass%. In the film forming step of the film described later, the solvent removed from the film by drying can be recovered and reused for the dissolution of cellulose acetate.

[0253] As a method for dissolving cellulose acetate when preparing a dope, a general method can be used. If heating and pressurization are combined, it is possible to heat to a temperature above the boiling point at normal pressure.

[0254] In addition, as a method for dispersing a filler when preparing a dope, a general method can be used.

[0255] Next, the cellulose acetate solution is filtered using a suitable filter material such as filter paper. As a filter material, the absolute filtration precision is preferably 0.008 mm or less, more preferably in the range of 0.001 to 0.008 mm, and further preferably in the range of 0.003 to 0.006 mm.

[0256] The filter material is not particularly limited, and a general filter material can be used. The filter material is, for example, plastic such as polypropylene, Teflon (registered trademark), or metal such as stainless steel, and the above materials are preferable because they do not have fiber shedding or the like.

[0257] The filtration of the paste can be performed using a general method. For example, the temperature of the filtration is preferably in the range of above the boiling point of the solvent at normal pressure and below the boiling point of the solvent under pressure. By heating while filtering, the increase in the difference in the filter pressure (pressure difference) before and after the filtration can be reduced. The temperature of the filtration is preferably in the range of 45 to 120°C, more preferably in the range of 45 to 70°C, and further preferably in the range of 45 to 55°C.

[0258] The filter pressure is preferably small. The filter pressure is preferably 1.6 MPa or less, more preferably 1.2 MPa or less, and further preferably 1.0 MPa or less.

[0259] (3.2) Step of casting the paste on a support to form a cast film

[0260] Next, the casting of the paste is described.

[0261] The metal support of the casting (pouring) step is preferably a support on which the surface has been mirror finished. As the metal support, for example, a stainless steel belt or a cylinder on which the surface has been plated is preferable. The width of the pouring is preferably in the range of 1 to 4 m.

[0262] The surface temperature of the metal support of the casting step is preferably -50°C or higher and less than the boiling point of the solvent, more preferably in the range of 0 to 40°C, and further preferably in the range of 5 to 30°C.

[0263] From the viewpoint of the good planarity of the optical film, the amount of the residual solvent at the time of peeling the sheet from the metal support is preferably in the range of 10 to 150 mass%. Further, it is more preferably in the range of 20 to 40 mass% or in the range of 60 to 130 mass%. Furthermore, it is further preferably in the range of 20 to 30 mass% or in the range of 70 to 120 mass%.

[0264] In the present application, the amount of the residual solvent is defined by the following formula.

[0265] Amount of residual solvent (mass%) = {(M - N) / N} x 100

[0266] It should be noted that M is the mass of a sample collected at any time during or after the manufacture of the sheet or film. N is the mass after heating M at 115°C for 1 hour.

[0267] (3.3) Step of peeling the cast film from the support

[0268] The sheet is peeled from the metal support. The method of peeling the sheet from the metal support can use a known method.

[0269] (3.4) Step of drying the cast film

[0270] In the drying step of the optical film, the web peeled from the metal support is further dried. The amount of residual solvent is preferably 1% by mass or less, more preferably 0.1% by mass or less, and further preferably in the range of 0 to 0.01% by mass.

[0271] In the drying step of the film, a drying method in which the web is dried while being conveyed by a roll drying method or a tenter method is generally used. In the roll drying method, the web is dried by alternately passing through a plurality of rolls arranged above and below.

[0272] The optical film is preferably stretched in the longitudinal direction (MD direction) at a position where the web has a large amount of residual solvent immediately after being peeled from the metal support. Further, the web is preferably stretched in the width direction (TD direction) by a tenter method in which both ends of the web are gripped by clips or the like.

[0273] The method of drying the web is not particularly limited, and generally, hot air, infrared rays, a heated roll, microwaves, and the like can be mentioned. From the viewpoint of convenience, drying by hot air is preferred.

[0274] The drying temperature in the drying step of the web is preferably in the range of 90°C to 200°C, and more preferably in the range of 110°C to 190°C. The drying temperature is preferably increased in stages.

[0275] The preferred drying time also depends on the drying temperature, but is preferably in the range of 5 minutes to 60 minutes, and more preferably in the range of 10 minutes to 30 minutes.

[0276] The thickness of the optical film is not particularly limited, and is preferably in the range of 10 to 200 μm, more preferably in the range of 10 to 100 μm, and preferably in the range of 20 to 60 μm.

[0277] The width of the optical film is preferably in the range of 1 to 4 m. From the viewpoint of productivity, the width is preferably in the range of 1.6 to 4 m, and more preferably in the range of 1.8 to 3.6 m.

[0278] (3.5) Stretching the Optical Film

[0279] The stretching operation can be performed sequentially or simultaneously in the longitudinal direction (MD direction) and the width direction (TD direction) of the film. The stretching ratio in the mutually orthogonal biaxial directions is preferably in the range of 1.0 to 2.0 times in the MD direction and 1.07 to 2.0 times in the TD direction, respectively, in the final product. Alternatively, the stretching ratio is preferably in the range of 1.0 to 1.5 times in the MD direction and 1.07 to 2.0 times in the TD direction, respectively.

[0280] For example, a method can be mentioned in which a circumferential speed difference is imparted to a plurality of rollers, and stretching in the MD direction is performed using the circumferential speed difference between the rollers. A method can be mentioned in which both ends of a web are fixed with clips or pins, and the web is stretched in the MD direction by expanding the interval of the clips or pins in the running direction, and likewise, a method in which the web is stretched in the TD direction by expanding in the transverse direction. In addition, a method in which the web is stretched in both the MD and TD directions by expanding in both directions at the same time in the film production process in the tenter, and the like, can be mentioned.

[0281] The maintaining of these widths or the stretching in the width direction in the film production process is preferably performed by a tenter, and can be either a pin tenter or a clip tenter.

[0282] The film transport tension in the film production process in the tenter, and the like, is preferably in the range of 120 to 200 N / m, more preferably in the range of 140 to 200 N / m, and further preferably in the range of 140 to 160 N / m, although it also depends on the temperature.

[0283] If the glass transition temperature of the optical film is set to Tg, the temperature of the optical film at the time of stretching is preferably in the range of (Tg - 30) to (Tg + 100) °C, more preferably in the range of (Tg - 20) to (Tg + 80) °C, and further preferably in the range of (Tg - 5) to (Tg + 20) °C.

[0284] The Tg of the optical film can be controlled by the kind of material constituting the film and the ratio of the materials constituting. The Tg of the film at the time of drying is preferably 110°C or higher, and more preferably 120°C or higher.

[0285] In addition, the Tg of the film at the time of drying is preferably 190°C or lower, and more preferably 170°C or lower. The Tg of the film can be found by a method described in JIS K7121, and the like.

[0286] By setting the temperature at the time of stretching to 150°C or higher and the stretching ratio to 1.15 times or higher, a roughness can be moderately imparted to the surface of the film. By moderately imparting a roughness to the surface of the film, not only smoothness but also surface processability and adhesion to an adjacent layer can be improved. The average surface roughness Ra of the optical film is preferably in the range of 2.0 to 4.0 nm, and more preferably in the range of 2.5 to 3.5 nm.

[0287] The average surface roughness Ra (nm) of the optical film and the polarity of the solvent with respect to the optical film itself preferably satisfy the following relational expression.

[0288] (Formula) Ra ≥ 3.5 x log P - 25.4

[0289] The optical film is preferably heat-set after stretching. The temperature at the time of heat-setting is preferably higher than the temperature at the time of the final stretching in the TD direction. The heat-setting is preferably performed at a temperature of (Tg - 20°C) or lower for usually 0.5 to 300 seconds. At this time, the heat-setting is preferably performed while sequentially increasing the temperature in a range where the temperature difference becomes 1 to 100°C, in the state where the film is divided into two or more regions.

[0290] The film after heat-setting is usually cooled to Tg or lower, and the film is wound while the clamps at both ends of the film are clamped. At this time, the film is preferably subjected to relaxation treatment in the TD direction and / or the MD direction at a temperature range of Tg or higher and lower than the final heat-setting temperature, at a rate of 0.1 to 10%.

[0291] The cooling is preferably performed at a cooling rate of 100°C / sec or lower from the final heat-setting temperature to Tg. The method of the cooling and the relaxation treatment is not particularly limited, and a publicly known method can be used. From the viewpoint of improving the dimensional stability of the film, these treatments are particularly preferably performed while sequentially cooling in a plurality of temperature regions.

[0292] Note that the cooling rate is a value obtained by (T1 - Tg) / t, where T1 is the final heat-setting temperature, and t is the time taken for the film to reach Tg from the final heat-setting temperature.

[0293] Further optimum conditions of these heat-setting conditions, cooling, and relaxation treatment conditions differ depending on the type of additives such as cellulose acetate, fillers, and plasticizers constituting the optical film. The physical properties of the biaxially stretched film obtained by measurement are appropriately selected to allow the optical film to have preferable properties.

[0294] 3. Glass Layer

[0295] The display device of the present application preferably further has a glass layer between the optical film and the color filter. By having the glass layer, the impact resistance of the display device can be further improved. Note that the glass layer (thin film glass) is excellent in the sense of luxury, durability (difficult to form a crease, etc.), planarity, and the like.

[0296] (1) Outline of Glass Layer (Thin Film Glass)

[0297] As the material of the thin film glass, for example, lithium aluminosilicate glass, soda-lime glass, borosilicate glass, silica glass, alkali aluminosilicate glass, and low-alkali-content aluminosilicate glass can be given.

[0298] The thin film glass is preferably an alkali-free glass which practically does not contain an alkali component. Specifically, the content of the alkali component is preferably 1000 mass ppm or less, more preferably 500 mass ppm or less, and further preferably 300 mass ppm or less, relative to the total mass of the thin film glass.

[0299] By reducing the alkali component, it is possible to suppress the replacement of cations on the surface of the thin film glass, and it is possible to suppress the phenomenon called alkali emission. Thus, it is possible to suppress the decrease in the density of the surface of the thin film glass, and it is possible to make it difficult to break.

[0300] The thickness of the thin film glass is preferably in the range of 10 to 50 μm. By setting the thickness of the thin film glass to 10 μm or more, sufficient impact resistance of the display device can be obtained. On the other hand, by setting the thickness of the thin film glass to 50 μm or less, sufficient flexibility of the display device can be obtained. In addition, the thinner the thickness of the thin film glass is set, the thinner the cover member can be made, and the thinner the display device can be made.

[0301] From the viewpoint of both impact resistance and flexibility, the thickness of the thin film glass is more preferably in the range of 10 to 40 μm, and further preferably in the range of 10 to 30 μm.

[0302] (2) Method for producing glass layer (thin film glass)

[0303] The thin film glass (glass layer) can be produced by a generally known method, for example, by a float method, a down-draw method, a flow-down-draw method, or the like. Among them, from the viewpoint of the surface of the thin film glass not being in contact with a forming member at the time of production, the surface of the thin film glass not being easily scratched, or the like, the flow-down-draw method or the float method is preferable. Among them, from the viewpoint of being able to obtain a thin film glass having a thickness in the range of 10 to 50 μm, the float method is preferable.

[0304] Generally, the thinner the thickness of the glass is, the lower the strength of the glass is, and the more easily the glass is broken, and thus, it is difficult to handle and process a single thin film glass. However, by temporarily adhering the thin film glass to a thicker support substrate (hereinafter, also referred to as a "carrier substrate") while processing, and peeling off the support substrate as a post-process of the processing, it is possible to make the handling and processing of the thin film glass easy.

[0305] For example, in the technology described in International Publication No. 2017 / 066924, a soda-lime glass having a thickness of less than 100 μm can be produced by the following procedure. Note that, Figure 5 is a schematic view showing one example of a method for producing a thin film glass.

[0306] (Step 1)

[0307] As shown in Figure 5 Step 1, a thin film glass 22 is produced on a carrier substrate 21 having a bonding surface in contact with a first surface of the thin film glass. Also, a contact film 23 (also referred to as a "touch film") having an adhesive force is pressure-bonded to a second surface opposite to the above-described first surface.

[0308] That is, a material of the thin film glass is cast on the carrier substrate 21 having a sufficient strength and a thickness easy to process in a manner to become a desired thickness. Thus, the first surface of the thin film glass 22 is produced in a manner to contact the carrier substrate 21. Then, the contact film 23 is pressure-bonded to the second surface opposite to the above first surface.

[0309] (Step 2)

[0310] As shown in FIG. 2, in Step 2, the thin film glass 22 is peeled from the carrier substrate 21 by the contact film 23 having a high adhesive force. Figure 5

[0311] (Step 3)

[0312] As shown in FIG. 3, in Step 3, a fragile treatment (electromagnetic radiation irradiation 24) to weaken the adhesive force of the contact film is performed. Thus, the contact film 23 is removed from the second surface of the thin film glass 22. Figure 5

[0313] Thus, by using the contact film 23 for safely holding the thin film glass 22, the thin film glass 22 can be protected. For example, the surface of the thin film glass 22 exposed can be protected from mechanical damage, and the handling can be safely and easily performed.

[0314] As the material of the contact film, for example, polyethylene terephthalate (PET), polyethylene (PE), and the like polyolefin (PO) can be given.

[0315] The contact film is usually adhered to the thin film glass by an adhesive layer composed of an adhesive provided on one face of a base material. The contact film can also be directly adhered to the thin film glass by the adhesiveness of the contact film itself.

[0316] The adhesive force between the contact film and the second surface of the thin film glass is appropriately selected in a manner to be able to transmit a sufficient force required to peel the thin film glass from the carrier substrate by a peeling device.

[0317] The shape of the contact film is preferably a foil or a tape. By being a foil or a tape, it can be wound into a roll shape. The thickness of the contact film is preferably 50 μm or more, preferably 80 μm or more, more preferably 125 μm or more, and particularly preferably 150 μm or more.

[0318] The thin film glass is preferably produced on the carrier substrate by the above-mentioned down-draw method, overflow down-draw method, or float method, and the like.

[0319] The thickness of the carrier substrate is preferably 100 μm or more, more preferably 300 μm or more, and further preferably 500 μm or more.

[0320] ​​In addition, the length of the carrier substrate in the width direction is preferably 3 inches (1 inch = 2.54 cm) or more, more preferably 6 inches or more, further preferably 8 inches or more, and particularly preferably 12 inches or more.

[0321] In particular, the carrier substrate is preferably a glass substrate of the first generation size or more, for example, the second to eighth generation size. Alternatively, it can be a larger size of 1 x 1 m to 3 x 3 m, for example. The carrier substrate can be rectangular, elliptical, circular, or the like.

[0322] The thin film glass is peeled from the carrier substrate with the adhesion of the contact film. Then, the contact film is peeled, and a single thin film glass is obtained.

[0323] It is preferable to perform a treatment for weakening the adhesion of the contact film before peeling the contact film from the thin film glass, thereby reducing the adhesion. Specifically, it is preferable to reduce the adhesion to 0.5 N / 25 mm or less.

[0324] In the weakening treatment, it is preferable to appropriately use electromagnetic radiation such as infrared rays, ultraviolet rays, and visible light. The electromagnetic radiation corresponds to the adhesion material used, and can be a narrow frequency band or can cover a wider frequency band. In addition, it can also be laser radiation.

[0325] Among them, it is preferable to select electromagnetic radiation having a wavelength outside the visible spectrum so that the adhesion does not deteriorate under exposure to visible light. Among commercially available adhesion materials, there are adhesion materials that can be at least partially inactivated by irradiation of electromagnetic radiation, and such adhesion materials can be used as the contact film.

[0326] In the case where the adhesion of the contact film is reduced by raising or lowering the temperature, a heat treatment can be used as the weakening treatment.

[0327] Irradiation of electromagnetic radiation is preferably performed from the outer side of the contact film, that is, from the side of the surface that is not adhered to the thin film glass.

[0328] As the contact film, for example, "NDS4150-20" (manufactured by DOW OCA LLC) or the like can be given. The weakening treatment corresponding thereto can be irradiation of ultraviolet rays having a wavelength of 365 nm.

[0329] The specific method and conditions for manufacturing the thin film glass are described in the items of the examples. In addition, as the thin film glass, commercially available products such as those manufactured by SCHOTT and Nippon Electric Glass Co., Ltd. can be used.

[0330] 4. Color filter

[0331] By providing the display device of the present application with a color filter, it is possible to display a desired color image.

[0332] The color display method of the display device of the present application is not particularly limited. In addition, the details will be described later, but as the light emitting element of the present application, an organic electroluminescence (EL) element is preferably used. Also, as the color display method using the organic EL element, any of the following methods can be used. Figures 6 to 9 A schematic view showing one example of the color display method preferably used in the present application.

[0333] However, the light emitting element is not limited to the organic EL element, and the present application can be applied even in the case where a color filter is used in other light emitting elements.

[0334] In the methods of 2) and 3) described below, the present application can be applied because a color filter must be used. Note that the type of the light emitting element is not particularly limited.

[0335] In addition, from the viewpoint of improving the color purity by the methods of 1) and 4) described below, the present application can be applied in the case where a color filter is used.

[0336] 1) A method in which light emitting layers 42 emitting each of R (red), G (green), and B (blue) colors are arranged laterally (see FIG. 1). Figure 6 ).

[0337] 2) A method in which white light 45 is arranged on the back surface and passes through an RGB color filter 46 (see FIG. 2). Figure 7 ).

[0338] 3) A method in which blue light 47 is arranged on the back surface and passes through a color filter (wavelength conversion film) 48, and a phosphor absorbs and emits red light (R) and green light (see FIG. 3). Figure 8 ).

[0339] 4) A method in which light emitting layers emitting each of R, G, and B colors are stacked vertically (see FIG. 4). Figure 9 ).

[0340] In the present application, the "color filter" refers to a filter having a function of transmitting visible light in a specific wavelength region and making the transmitted light a desired color tone. The display device of the present application can present a desired color by having a color filter. In addition, the color reproduction degree can be improved.

[0341] In addition, the "aperture ratio" refers to the proportion of the area of a region (a region other than a black matrix) in which visible light is transmitted to the area of the entire region in which visible light in a specific wavelength region is irradiated.

[0342] Note that each of the regions in which visible light is transmitted corresponds to a pixel.

[0343] Figure 10is a schematic view of a color filter. The color filter 60 is composed of a black matrix 51 that does not transmit visible light and a transmission region 52 that transmits visible light. In the transmission region 52, color pixels are arranged as needed so that the transmitted light becomes a desired color tone. In the color filter 60, a region that transmits visible light of a specific wavelength region is indicated as a transmission region 53 (the inside of the dotted line).

[0344] The aperture ratio of the present application is represented by the proportion of the area of the transmission region 52 with respect to the area of the transmission region 53.

[0345] By appropriately adjusting the aperture ratio of the color filter, a function of preventing reflection of light incident from the outside can be imparted. Furthermore, without reintroducing a circularly polarizing plate, a display device with excellent visibility can be obtained. Furthermore, since a circularly polarizing plate does not need to be introduced, the display device can be further thinned.

[0346] The aperture ratio of the color filter is preferably in the range of 65 to 90%, and more preferably in the range of 65 to 80%. By being in the above range, the reflectance of light incident from the outside can be reduced, and the color reproduction degree can be improved.

[0347] In addition, even in the above 1) and 4) methods in which a color filter is not necessarily required, by using a color filter and adjusting the aperture ratio, a display device with excellent visibility can be obtained without introducing a circularly polarizing plate. That is, the display device can be further thinned, and the color reproduction degree can be improved.

[0348] The color filter of the present application can use a conventionally known color filter.

[0349] The color filter has a color layer composed of a black matrix and a color pixel on one face of a transparent substrate. Note that the black matrix is preferably formed in a lattice shape or a stripe shape between the color pixels.

[0350] In addition, a fixed spacer, an overcoat layer, etc. can be provided as needed.

[0351] The color layer is preferably formed by a colored resin composition.

[0352] The colored resin composition is prepared by mixing, for example, a colorant, a binder resin, a photopolymerizable monomer, a photopolymerization initiator, an additive, an organic solvent, etc.

[0353] As the colorant, conventionally known red pigments, green pigments, yellow pigments, blue pigments, violet pigments, black pigments, etc. can be used. In addition, a color conversion material (inorganic or organic fluorescent material) can be used as needed.

[0354] As the additive, for example, a surfactant, a chain transfer agent, a storage stabilizer, etc. can be used.

[0355] The colored resin composition is preferably prepared in the form of a printing ink for gravure offset printing, a non-aqueous offset printing ink, an ink for inkjet, an ink for screen printing, a colored resist of the solvent development type or the alkali development type.

[0356] The content of the colorant is preferably in the range of 5 to 70% by mass, more preferably in the range of 20 to 50% by mass, relative to the total mass of the solid components of the colored resin composition.

[0357] The colored resin composition is preferably subjected to removal of coarse particles of 5 μm or more, preferably coarse particles of 1 μm or more, more preferably coarse particles of 0.5 μm or more, and dust mixed therein, using a centrifugal separator, a sintered filter, a membrane filter, or the like.

[0358] As the method of forming the colored pixels, photolithography is preferable. The colored resin composition is prepared as a colored resist of the solvent development type or the alkali development type. Further, a coating method such as spray coating, spin coating, slit coating, roll coating, or the like is preferably used to coat the composition on an array substrate in such a manner that the thickness of the dried coating film becomes in the range of 0.2 to 10 μm.

[0359] As the method of drying the coating film, a reduced-pressure drier, a convection oven, an IR oven, a hot plate, or the like can be used. Then, ultraviolet light exposure is performed through a mask having a prescribed pattern provided in contact with or not in contact with the dried coating film. In confirming the alignment marks with the mask, infrared light having a wavelength in the range of 750 to 1000 nm is used.

[0360] Then, the uncured portions are removed by immersing in an organic solvent or an alkali developing solution, or by spraying the developing solution through a sprayer, to form the desired pattern. Further, the same operation is repeated for other colors to form the colored pixels of the color filter.

[0361] In the development, an aqueous solution of sodium carbonate, sodium hydroxide, or the like can be used as the alkali developing solution. Alternatively, an organic base such as dimethylbenzylamine, triethanolamine, or the like can be used. Further, a defoaming agent, a surfactant, or the like can be added to the developing solution. As the development method, for example, a spray development method, a spray development method, a dip development method, an immersion development method, or the like can be used.

[0362] The thickness of the color filter is preferably in the range of 1 to 5 μm. By being 1 μm or more, the color purity can be further improved, and by being 5 μm or less, the brightness can be improved.

[0363] 5. Light-emitting element

[0364] The display device of the present application has a light-emitting element. Note that the "light-emitting element" refers to a general term for electronic components that convert an electric signal into an optical signal.

[0365] In the present application, the light-emitting element is not particularly limited, and examples thereof include an organic electroluminescence (EL) element, an inorganic EL element, a quantum dot light-emitting element, and the like.

[0366] Among them, from the viewpoints of flexibility and thinness, an organic EL element is preferred. As the organic EL element, a conventionally known element can be used. As one example, an element composed of an electrode / electron-transporting layer / light-emitting layer / hole-transporting layer / transparent electrode.

[0367] 6. A manufacturing method of a display device

[0368] The display device of the present application can be manufactured by adhering the above light-emitting element, color filter, and cover member with an adhesive or the like.

[0369] The manufacturing method is not particularly limited, and a conventionally known method can be used.

[0370] The adhesive is not particularly limited, and examples thereof include a rubber-based adhesive, an acrylic-based adhesive, a silicone-based adhesive, a urethane-based adhesive, a vinyl alkyl ether-based adhesive, a polyvinyl alcohol-based adhesive, a polyvinyl pyrrolidone-based adhesive, a polyacrylamide-based adhesive, a cellulose-based adhesive, and the like. Among them, an acrylic-based adhesive is preferred. An acrylic-based adhesive is excellent in transparency and adhesive properties (adhesion, cohesion, and tackiness). In addition, it is also excellent in weather resistance, heat resistance, and the like.

[0371] Note that, here, the "acrylic-based adhesive" refers to an adhesive containing an acrylic-based polymer as a base polymer.

[0372] 7. Product example of a display device

[0373] The display device of the present application is characterized by having at least the above light-emitting element, color filter, and cover member.

[0374] In the present application, the "display device" refers to a device having a display mechanism.

[0375] As the display device, examples thereof include a liquid crystal display device, an organic electroluminescence (EL) display device, an inorganic EL display device, a touch panel display device, an electron emission display device (field emission display device (FED), surface-conduction electron-emitter display device (SED)), electronic paper (a display device using electronic ink, an electrophoretic element), a plasma display device, a projection display device (grating light valve (GLV) display device, a display device having a digital micromirror device (DMD), and the like), a piezoelectric ceramic display, and the like.

[0376] Further, as the liquid crystal display device, there can be mentioned a transmissive liquid crystal display device, a transflective liquid crystal display device, a reflective liquid crystal display device, a direct view liquid crystal display device, a projection liquid crystal display device, and the like.

[0377] These display devices can be display devices displaying two-dimensional images, or stereoscopic display devices displaying three-dimensional images.

[0378] Among them, from the viewpoint of flexibility and thinness, as the display device of the present application, an organic EL display device is preferable. Further, from the viewpoint of having a cover member having excellent impact resistance, a touch panel display device is preferable.

[0379] Further, the display device of the present application is preferably a flexible display. As the flexible display, there can be mentioned, for example, a folding display. The folding display is preferably a structure in which 1 continuous display is folded into two parts at the time of carrying, thereby halving the size, and thus improving portability. The folding display is further preferably thin and light.

[0380] Note that "flexible" means capable of being bent or curved, and the state of being capable of being bent or curved also includes being bent or curved. Specifically, the radius of curvature of the state of being capable of being bent or curved is preferably 10 mm or less, and more preferably 3 mm or less. In particular, if the radius of curvature is 3 mm or less, the display can also be used by being folded.

[0381] The display device of the present application has excellent impact resistance by having a cover member. Further, the optical film satisfies specific conditions, and thus sufficient visibility can be obtained even without using a circularly polarizing plate. That is, the display device of the present application is thin and has excellent visibility.

[0382] Further, in the case where a folding display is produced, even after repeatedly folding the display, the visibility is excellent. Specifically, distortion of an image is difficult to occur at the folding position of the display.

[0383] Therefore, for example, in a portable terminal device in which a folding display is mounted, a beautiful image can be provided, and the functionality is rich and the convenience such as portability is excellent.

[0384] Examples

[0385] Hereinafter, the present application will be specifically described by using examples, but the present application is not limited to these. Note that in the examples, although expressions of "parts" or "%" are used, "parts by mass" or "%" is meant unless otherwise specified.

[0386] Further, in the following examples, unless otherwise specified, the operations were performed at room temperature (25°C).

[0387] 1. Production of Display Device

[0388] (1) Production of optical film

[0389] (1.1) Production of optical film 1

[0390] (1.1.1) Preparation of cellulose acetate

[0391] Cellulose acetate having a degree of substitution of 2.45 was prepared by a known method.

[0392] (1.1.2) Production of filler

[0393] (1.1.2.1) Production of filler 1

[0394] A 500 mL four-necked flask was charged with ion exchange water 130 g and acetic acid 8.8 g (0.146 mol). The mixture was heated to 30°C (liquid temperature) while stirring. Aluminum isopropoxide 27 g (0.132 mol) was added dropwise to the mixture over 30 minutes. Then, the mixture was heated to 95°C (liquid temperature) while distilling off isopropyl alcohol from the mixture, and hydrolysis was performed at 95°C for 30 minutes.

[0395] Next, the mixture was stirred in an autoclave at 150°C for 6 hours. After the lapse of the prescribed time, the reaction solution was cooled to room temperature (25°C) to obtain a solution containing alumina filler precursor 1 (solid content concentration: about 5 mass %). Here, the average diameter and the average length of the alumina filler precursor 1 were 4 nm and 3000 nm, respectively (aspect ratio = 750).

[0396] The solution containing alumina filler precursor 1 50 g, methyl isobutyl ketone 50 g, and dodecylbenzenesulfonic acid 0.4 g were mixed. Next, the mixture was subjected to dehydration treatment using a Dean-Stark apparatus. Then, a methyl isobutyl ketone dispersion of alumina filler precursor 1 surface-modified with dodecylbenzenesulfonic acid was obtained. The thus obtained alumina filler was used as filler 1.

[0397] The minor axis (y) and the major axis (x) of the obtained filler 1 were 4 nm and 3000 nm, respectively (aspect ratio (x / y) = 750). Note that in this example, the minor axis and the major axis of the filler 1 correspond to the average diameter and the average length, respectively.

[0398] (1.1.2.2) Production of fillers 2 to 5

[0399] In the production of the above-described filler 1, fillers 2 to 5 were produced in the same procedure except that the amount of acetic acid was changed. Note that the aspect ratios of the respective fillers are as described in Table I.

[0400] (1.1.2.3) Production of filler 6

[0401] In the production of the above filler 1, an alumina filler precursor 1 was produced in the same procedure. Next, 50 g of the alumina filler precursor 1, 50 g of methyl isobutyl ketone and 0.4 g of benzoic acid were mixed. The mixture was subjected to dehydration treatment using a distillation apparatus. Then, a methyl isobutyl ketone dispersion of the alumina filler precursor 1 surface-modified with benzoic acid was obtained. The thus obtained alumina filler was used as filler 6.

[0402] The short diameter (y) and the long diameter (x) of the obtained filler 6 were 4 nm and 3000 nm, respectively (long diameter ratio (x / y) = 750). Note that in this example, the short diameter and the long diameter of the filler 6 correspond to the average diameter and the average length, respectively.

[0403] (1.1.2.4) Production of filler 7

[0404] In the production of the above filler 1, an alumina filler precursor 1 was produced in the same procedure. Next, 50 g of the alumina filler precursor 1, 50 g of methyl isobutyl ketone and 0.4 g of benzoic acid were mixed. The mixture was subjected to dehydration treatment using a distillation apparatus. Then, a methyl isobutyl ketone dispersion of the alumina filler precursor 1 surface-modified with benzoic acid was obtained. The thus obtained alumina filler was used as filler 6. n -P(=0)-(OH) 3-n Note that n here is 1 or 2. The thus obtained alumina filler was used as filler 7.

[0405] The short diameter (y) and the long diameter (x) of the obtained filler 7 were 4 nm and 3000 nm, respectively (long diameter ratio (x / y) = 750). Note that in this example, the short diameter and the long diameter of the filler 7 correspond to the average diameter and the average length, respectively.

[0406] (1.1.2.5) Production of filler 8

[0407] In a 500 mL four-necked flask, 130 g of ion exchange water and 8.8 g (0.146 mol) of acetic acid were charged. The mixture was heated to 30°C (liquid temperature) while stirring. Tetraethyl orthosilicate 30 g (0.142 mol) was added dropwise to the mixture over 30 minutes. Then, the mixture was heated to 95°C (liquid temperature) while distilling off ethanol, and hydrolysis was performed at 95°C for 30 minutes.

[0408] Next, the mixture was stirred in an autoclave while performing a reaction at 150°C for 6 hours. After the reaction was performed for the prescribed time, the reaction liquid was cooled to room temperature (25°C) to obtain a solution containing the silica filler precursor (solid content concentration: about 5 mass %). Here, the average diameter and the average length of the silica filler precursor were 4 nm and 3000 nm, respectively (aspect ratio = 750).

[0409] The solution containing the silica filler precursor 50 g, methyl isobutyl ketone 50 g, and dodecylbenzenesulfonic acid 0.4 g were mixed. Dehydration treatment of the mixture was performed using a Dean-Stark apparatus. Then, a methyl isobutyl ketone dispersion of the silica filler precursor surface-modified with dodecylbenzenesulfonic acid was obtained. The silica filler thus obtained was used as the filler 8.

[0410] The minor axis (y) and the major axis (x) of the filler 8 obtained were 4 nm and 3000 nm, respectively (aspect ratio (x / y) = 750). Note that in this example, the minor axis and the major axis of the filler 8 correspond to the average diameter and the average length, respectively.

[0411] (1.1.2.6) Production of Filler 9

[0412] An ion exchange water 130 g and acetic acid 8.8 g (0.146 mol) were charged in a 500 mL four-necked flask. The mixture was heated to 30°C (liquid temperature) while stirring. Tetraethyl orthotitanate 30 g (0.142 mol) was added dropwise to the mixture over 30 minutes. Then, the mixture was heated to 95°C (liquid temperature) while distilling off ethanol, and hydrolysis was performed at 95°C for 30 minutes.

[0413] Next, the mixture was stirred in an autoclave while performing a reaction at 150°C for 6 hours. After the reaction was performed for the prescribed time, the reaction liquid was cooled to room temperature (25°C) to obtain a solution containing the silica filler precursor (solid content concentration: about 5 mass %). Here, the average diameter and the average length of the silica filler precursor were 4 nm and 3000 nm, respectively (aspect ratio = 750).

[0414] The solution containing the titanium oxide filler precursor 50 g, methyl isobutyl ketone 50 g, and dodecylbenzenesulfonic acid 0.4 g were mixed. Dehydration treatment of the mixture was performed using a Dean-Stark apparatus. Then, a methyl isobutyl ketone dispersion of the titanium oxide filler precursor surface-modified with dodecylbenzenesulfonic acid was obtained. The titanium oxide filler thus obtained was used as the filler 9.

[0415] The short diameter (y) and long diameter (x) of the obtained filler 9 were 4 nm and 3000 nm, respectively (long diameter ratio (x / y) = 750). Note that in this example, the short diameter and long diameter of the filler 9 correspond to the average diameter and average length, respectively.

[0416] (1.1.2.7) Production of fillers 10 and 11

[0417] Strontium carbonate filler precursors and barium carbonate filler precursors each having an average diameter and an average length of 4 nm and 3000 nm (long diameter ratio = 750), respectively, were produced using a known method.

[0418] Next, 50 g of each of the filler precursors produced, 50 g of methyl isobutyl ketone, and 0.4 g of glycerol stearate were mixed. Dehydration treatment of the mixture was performed using a distillation apparatus. Then, a methyl isobutyl ketone dispersion of each of the filler precursors 1 surface-modified with glycerol stearate was obtained. The strontium carbonate filler thus obtained was used as the filler 10, and the barium carbonate filler was used as the filler 11.

[0419] The short diameter (y) and long diameter (x) of the obtained fillers 10 and 11 were 4 nm and 3000 nm, respectively (long diameter ratio (x / y) = 750). Note that in this example, the short diameter and long diameter of the fillers 10 and 11 correspond to the average diameter and average length, respectively.

[0420] (1.1.3) Preparation of a paste

[0421] (1.1.3.1) Preparation of paste 1

[0422] (Silica dispersion)

[0423] "Aerosil (registered trademark) R812" (manufactured by Nippon Aerosil Co., Ltd., average diameter of primary particles: 7 nm)

[0424] 10.00 parts by mass of ethanol 90.00 parts by mass

[0425] After the above components were mixed by stirring for 30 minutes using a dissolver, a silica dispersion was prepared by dispersion using a Manton-Gaulin. The silica dispersion was filtered using a fine particle dispersion dilution filter (ADVANTEC Toyo Kaisha, Ltd.: polypropylene-wound filter TCW-PPS-1N).

[0426]

[0427] The above components were stirred at 23°C for 1 hour, and then 12 parts by mass of cellulose acetate was added, and stirred at 23°C for 4 hours. Then, filtration was performed using Advantec filter paper No. 24 manufactured by Advantec Toyo Kaisha, Ltd., to prepare paste 1.

[0428] Note that the content of the silica was 0.1 mass% relative to the total mass of the cellulose acetate. Also, the content of the filler 1 was 5 mass% relative to the total mass of the cellulose acetate.

[0429] (1.1.3.2) Preparation of the paste 2 to 15

[0430] In the preparation of the above paste 1, the paste 2 to 15 was prepared in the same procedure except that the resin and the filler were changed as described in Table I.

[0431] (1.1.4) Formation of the optical film

[0432] (1.1.4.1) Formation of the optical film 1

[0433] Next, the above paste 1 was uniformly cast on a stainless steel belt support using a belt casting apparatus to form a cast film. The cast film was peeled off from the stainless steel belt support after the evaporation of the solvent to 100% of the residual solvent amount of the cast film on the stainless steel belt support. The cast film was heated at 35°C to evaporate the solvent. Then, the cast film after the evaporation of the solvent was cut to a width of 1.65 m, held by a tenter, and dried at a drying temperature of 160°C. Note that the drying temperature here can be the heat treatment temperature and the stretching temperature.

[0434] The residual solvent amount at the start of the drying was 20%. Then, the film was dried in a drying apparatus at 120°C for 15 minutes while being conveyed by a plurality of rollers, and then knurling processing was performed on both ends of the film to a width of 15 mm and a height of 10 μm. The film was wound on a winding core to obtain the optical film 1. The residual solvent amount of the optical film 1 was 0.2%, and the thickness was 40 μm, and the winding number was 6000 m.

[0435] (1.1.4.2) Production of the optical films 2 to 15

[0436] In the production of the above optical film 1, the optical films 2 to 15 were obtained in the same procedure except that the resin and the filler were changed as described in Table I.

[0437] Table I shows the composition of the optical films 1 to 15.

[0438] As the filler, alumina, silica, and titanium dioxide are metal oxides, and strontium carbonate and barium carbonate are metal salts.

[0439] "-" in the table indicates a non-conforming case.

[0440] Note that, for the "acrylic resin" in the table, an MMA (methyl methacrylate) / PMI (phenyl maleimide) / MA (methacrylic acid ester) copolymer (85 / 10 / 5 mass ratio, Mw: 2 million, Tg: 122°C) was used as the thermoplastic (meth) acrylic resin.

[0441] [Table 1]

[0442] Table I

[0443]

[0444] (2) Production of the glass layer

[0445] A glass layer (soda-lime glass) having a size of 12 inches was produced according to the following procedure.

[0446] (Procedure 1) A thin film glass was produced on a carrier substrate having a bonding surface in contact with the first surface of the thin film glass. Then, a contact film (also referred to as "Contact film") having an adhesive force was attached to the second surface opposite the first surface of the thin film glass.

[0447] (Procedure 2) Next, the thin film glass was peeled from the carrier substrate using the contact film having a high adhesive force.

[0448] (Procedure 3) The contact film was removed from the second surface of the thin film glass peeled from the carrier substrate by a weakening treatment (electromagnetic radiation irradiation) to weaken the adhesive force of the contact film.

[0449] After the thin film glass was produced in contact with a carrier substrate having a thickness of 500 μm and in a manner to have a prescribed thickness by Procedure 1, the following contact film was attached. Next, the thin film glass was peeled from the carrier substrate together with the contact film for 30 seconds by Procedure 2.

[0450] Note that the contact film used was a commercially available "NDS4150-20". The "NDS4150-20" is a film having a thickness of 150 μm containing a polyolefin (PO), and has an adhesive layer having a thickness of 10 μm.

[0451] Next, the exposed contact film was subjected to a weakening treatment to reduce the adhesive force by Procedure 3. In the weakening treatment, the contact film was irradiated with ultraviolet rays having a wavelength of 365 nm for 10 seconds. The irradiance of the ultraviolet rays was 500 mW / cm 2 , and the cumulative light amount was 500 mJ / cm 2 . The adhesive force before the weakening treatment was 11 N / 25 mm, and the adhesive force after the weakening treatment was reduced to 0.4 N / 25 mm. Thus, the contact film could be easily peeled from the thin film glass, and a glass layer having a thickness of 30 μm was obtained.

[0452] (3) Production of the adhesive layer

[0453] (3.1) Preparation of the ultraviolet-curable acrylic adhesive composition (a-1)

[0454] A monomer mixture consisting of the following components was prepared.

[0455] 2-Ethylhexyl acrylate (2EHA) 78 parts by mass N-Vinyl-2-pyrrolidone (NVP) 18 parts by mass 2-Hydroxyethyl acrylate (HEA) 4 parts by mass Further, the following component was added as a photopolymerization initiator.

[0456] 1-Hydroxycyclohexyl phenyl ketone 0.035 parts by mass 2,2-Dimethoxy-1,2-diphenylethan-1-one 0.035 parts by mass Note that the photopolymerization initiator used was a commercially available product as follows.

[0457] 1-Hydroxycyclohexyl phenyl ketone: "Omnirad (registered trademark) 184" (having an absorption band at a wavelength of 200 to 370 nm, manufactured by IGM Resins B.V.)

[0458] 2,2-Dimethoxy-1,2-diphenylethan-1-one: "Omnirad (registered trademark) 651" (having an absorption band at a wavelength of 200 to 380 nm, manufactured by IGM Resins B.V.)

[0459] Then, ultraviolet rays were irradiated until the viscosity (measuring conditions: BH viscometer No. 5 rotor, 10 rpm, measurement temperature 30°C) was about 20 Pa-s. Then, a prepolymer composition in which a part of the above-described monomer components was polymerized (polymerization rate: 8%) was obtained.

[0460] Next, the prepolymer composition was added with the following components and mixed to obtain an acrylic adhesive composition.

[0461] Hexanediol diacrylate (HDDA) 0.15 parts by mass Silane coupling agent "KBM-403" (manufactured by Shin-Etsu Chemical Co., Ltd.) 0.3 parts by mass

[0462] The following components were added to the obtained acrylic adhesive composition and stirred to thereby obtain the ultraviolet-curable acrylic adhesive composition (a-1).

[0463] 2,4-Bis-[{4-(4-ethylhexyloxy)-4-hydroxy}-phenyl]-6-(4-methoxyphenyl)-1,3,5-triazine

[0464] (added by dissolving in n-butyl acrylate at a solid content of 15 mass %)

[0465] 1.4 parts by mass

[0466] Bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide 0.2 parts by mass

[0467] Note that the following commercially available products were used.

[0468] 2,4-bis-[{4-(4-ethylhexyloxy)-4-hydroxy}-phenyl]-6-(4-methoxyphenyl)-1,3,5-triazine: "Tinosorb (registered trademark) S" (manufactured by BASF Japan Ltd.)

[0469] Bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide: "Omnirad (registered trademark) 819" (having an absorption band at a wavelength of 200 to 450 nm, manufactured by IGM Resins B.V.)

[0470] (3.2) Formation of the adhesive layer

[0471] The obtained ultraviolet-curable acrylic adhesive composition (a-1) was applied to a face of a release film at a thickness of 5 μm after curing, and further, a release film was attached to the surface after application. Then, ultraviolet irradiation was performed under conditions of illuminance: 6.5 mW / cm 2 , cumulative light amount: 1500 mJ / cm 2 to cure the composition, thereby peeling the release film to form an adhesive layer.

[0472] (4) Production of the color filter

[0473] (4.1) Preparation of the resin solutions (A-1) and (A-2)

[0474] A mixture of the following monomers and a thermal polymerization initiator was added dropwise to a reaction vessel to which cyclohexanone 800 parts by mass was added while heating with injection of nitrogen, thereby performing a polymerization reaction.

[0475]

[0476]

[0477] After the dropwise addition, heating was performed sufficiently, and then a solution in which the thermal polymerization initiator 2 parts by mass was dissolved in cyclohexanone 50 parts by mass was added, and further, the reaction was continued to obtain a solution of the acrylic resin.

[0478] Cyclohexanone was added to the resin solution so that the nonvolatile content was 20 mass%, thereby preparing an acrylic resin solution as resin solution (A-1).

[0479] The weight average molecular weight of the acrylic resin was about 30000.

[0480] Cyclohexanone 800 parts by mass was added to a reaction vessel, and the vessel was heated while nitrogen was injected thereto. A mixture of the following monomers and thermal polymerization initiator was added dropwise, and a polymerization reaction was performed.

[0481]

[0482] After the dropwise addition, the mixture was heated sufficiently, and a solution of thermal polymerization initiator 2 parts by mass dissolved in cyclohexanone 500 parts by mass was added, and the reaction was further continued to obtain a solution of acrylic resin.

[0483] Cyclohexanone was added to the resin solution so that the solid content was 30 mass%, thereby preparing an acrylic resin solution as resin solution (A-2).

[0484] The weight average molecular weight of the acrylic resin was about 20000.

[0485] (4.2) Preparation of the Resin Composition Containing Pigment

[0486] <Red Resin Composition>

[0487] A mixture of the following composition was stirred and mixed to be uniform, and then filtered with a filter of 5 μm to obtain a red resin composition.

[0488]

[0489]

[0490] <Green Resin Composition>

[0491] Then, a mixture of the following composition was stirred and mixed to be uniform, and then filtered with a filter of 5 μm to obtain a green resin composition.

[0492]

[0493] <Blue Resin Composition>

[0494] Then, a mixture of the following composition was stirred and mixed to be uniform, and then filtered with a filter of 5 μm to obtain a blue resin composition.

[0495]

[0496]

[0497] <Black Resin Composition>

[0498] Then, a mixture of the following composition was stirred and mixed to make it uniform, and then filtered with a 5 μm filter to obtain a black resin composition.

[0499]

[0500] Note that the above black pigment dispersion liquid was prepared by the following method.

[0501] After a mixture of the following composition was stirred and mixed for 30 minutes with a dissolver, it was dispersed for 30 minutes using an ultrasonic disperser. The resulting dispersion liquid was filtered with a polypropylene-wound filter "TCW-1N-PPS" (manufactured by ADVANTEC TOYO KAISHA, LTD.) to obtain a black pigment dispersion liquid.

[0502] Carbon black "#950" (manufactured by Mitsubishi Chemical Corporation) 10.0 parts by mass Methyl ethyl ketone 90.0 parts by mass (4.3) Formation of Black Matrix

[0503] The above black coloring composition was uniformly applied to a glass substrate by a spray coating method, and dried. Next, using a photolithography method, the glass substrate was exposed to ultraviolet rays through a photomask having a desired light-shielding pattern. Then, using a developer composed of sodium carbonate, the unexposed portions to the ultraviolet rays were washed away by a spray developing method to form a desired pattern. After development, the pattern was cured by performing a heat treatment at 230°C for 60 minutes after sufficient water washing and drying, to form a black matrix.

[0504] (4.4) Formation of Colored Pixels and Colored Pixel Lamination Spacer

[0505] The above red resin composition was uniformly applied to the glass substrate on which the black matrix was formed by a spray coating method, and dried. Next, using a photolithography method, the glass substrate was exposed to ultraviolet rays through a photomask having a desired light-shielding pattern, with respect to the region where the red pixels were to be formed and the region where the colored pixel lamination spacer was to be formed. Then, using a developer composed of sodium carbonate, the unexposed portions to the ultraviolet rays were washed away by a spray developing method to form a desired pattern. After development, the pattern was cured by performing a heat treatment at 230°C for 20 minutes after sufficient water washing and drying.

[0506] Using the above green resin composition, a green pattern was formed in the region where the green pixels were to be formed and the region where the colored pixel lamination spacer was to be formed, in the same procedure as the formation of the red pattern.

[0507] Using the above-described blue resin composition, a blue pattern is formed in the same procedure as that for the red pattern, in the region where a blue pixel is to be formed and in the region where the colored pixel layer-stacking partition is to be formed. At this time, the blue color of the uppermost portion of the colored pixel layer-stacking partition is integrated by covering the red color of the first layer and the green color of the second layer, thereby forming a colored layer composed of three colors of red (R), green (G), and blue (B) and the colored pixel layer-stacking partition.

[0508] The opening ratio of the obtained color filter was 77%.

[0509] (5) Production of Light Emitting Element (Organic Electroluminescent Element)

[0510] A bottom emission type organic EL element was produced according to the following method.

[0511] (5.1) Production of First Substrate with Gas Barrier Layer

[0512] A varnish having a thickness of 50 μm was spin-coated on a support glass having a thickness of t = 0.7 mm. Subsequently, post-baking was performed at 200°C for 20 minutes, and a flexible film substrate having a size of 30 cm x 40 cm was obtained as the first substrate.

[0513] A polysilazane-containing coating solution described below was applied to the varnish substrate using a wire bar so as to have an average film thickness of 300 nm after drying, and was subjected to a heating treatment and drying in an atmosphere having a temperature of 85°C and a humidity of 55% RH for 1 minute. Subsequently, the polysilazane-containing layer was formed on the varnish substrate by subjecting the polysilazane-containing coating solution to a dehumidification treatment by maintaining the atmosphere at a temperature of 25°C and a humidity of 10% RH (dew point temperature -8°C) for 10 minutes.

[0514] Subsequently, the varnish substrate on which the polysilazane-containing layer was formed was fixed to the operation table of an excimer irradiation device "MECL-M-1-200" (manufactured by M. D. COM Co., Ltd.). Then, a modification treatment was performed under the following conditions, and a polysilazane modification layer having a thickness of 300 nm was formed as a gas barrier layer, thereby obtaining the first substrate with a gas barrier layer.

[0515] (Polysilazane-containing Coating Solution)

[0516] A 10 mass% solution of perhydropolysilazane "AQUAMICA (registered trademark) NN120-10, catalyst-free type" (manufactured by Merck Co., Ltd.) in dibutyl ether was prepared as the polysilazane-containing coating solution.

[0517] (Modification Treatment Conditions)

[0518] Irradiation wavelength: 172 nm

[0519] Lamp-enclosed gas: Xe

[0520] Light intensity of excimer lamp: 130 mW / cm 2 (172 nm)

[0521] Distance of polysilazane containing layer from light source: 1 mm

[0522] Workbench heating temperature: 70°C

[0523] Oxygen concentration in irradiation device: 0.5 vol%

[0524] Excimer lamp irradiation time: 5 seconds

[0525] The first substrate with the barrier layer was cleaned by a wet cleaning method.

[0526] The alkaline cleaning agent was diluted to 5 mass%, the resulting cleaning agent solution was heated to 60°C, the first substrate was immersed in the cleaning agent solution at 60°C, and the first substrate was subjected to a scrub cleaning to remove foreign matter adhered to the first substrate. Next, the first substrate was subjected to an ultrasonic cleaning process, a pure water rinse, a nitrogen stream, and an IR (Infra Red) drying, in this order. Then, the first substrate was subjected to UV (Ultra Violet) irradiation, and the first substrate was dried using an oven after removing organic matter adhered to the surface of the first substrate.

[0527] (5.2) Fabrication of TFT unit

[0528] First, a SiO film was formed on the base layer by CVD, a gate electrode was formed, and then an a-Si:H film was formed as a gate insulating film by CVD, and then an n+a-Si:H film was formed as a channel layer by CVD. Then, dry etching was performed to form a desired pattern shape.

[0529] Next, after forming a source electrode and a drain electrode, a passivation film was formed. Also, a TFT of a-Si having an electrode width of 100 μm, a thickness of 200 nm, a channel width W = 3 mm, and a channel length L = 20 μm was formed at a position corresponding to the above-described color filter.

[0530] Meanwhile, an ITO was used to form a lead electrode of the first electrode, and a TFT unit was fabricated.

[0531] (5.3) Fabrication of organic EL element

[0532] Next, a white tandem organic EL element was formed on the first substrate and the TFT unit.

[0533] In the fabrication of the TFT unit, an ITO was used as a lead electrode for the organic EL element, and for the organic EL element (OLED), the ITO was used as the first electrode (anode) to fabricate.

[0534] Next, an organic functional layer group (7) composed of a first positive hole transport layer / a first light emitting layer / a first electron transport layer / an intermediate connector layer / a second positive hole transport layer / a second light emitting layer / a second electron transport layer was formed according to the method (Example) described in paragraphs (0201) to (0219) of Japanese Patent Application Publication No. 2015-201508.

[0535] Next, aluminum was vapor-deposited at a thickness of 150 nm to form a second electrode (cathode). For the organic EL element produced, the CIE chromaticity of the light emitting layer under the condition of emitting light without passing through the color filter of the present application was adjusted in a manner such that the same CIE chromaticity was obtained under the same light emitting condition as the D65 standard light source. In addition, as the method of forming each layer described above that constitutes the organic EL element, an inkjet printing method was used for the formation.

[0536] Next, on the second electrode, under a film formation pressure condition of 50 Pa, silane gas and ammonia gas were supplied, and a silicon nitride film having a thickness of 500 nm was formed by a plasma CVD method. This was used as a first sealing layer.

[0537] Specifically, the first substrate formed on the second electrode was placed in a vacuum chamber that was reduced in pressure to 1 x 10 -4 Pa or less. The temperature of the first substrate was adjusted to about 70°C, and as the reaction gas described above, SiH4 gas and NH3 gas, H2 gas were introduced into the vacuum chamber at a ratio of 2:1:4. In the vacuum chamber reduced in pressure to 50 Pa, film formation was performed by a plasma CVD method with a high frequency power source having a frequency of 13.56 MHz. The film formation was performed while cooling the first substrate in a manner such that the temperature of the first substrate was 70°C during the film formation. In this way, a first sealing layer composed of SiN having a thickness of 500 nm was formed.

[0538] Next, a second sealing layer was formed. On the first sealing layer formed as described above, AlPET to which a thermosetting adhesive was applied was attached. The AlPET was used to prevent moisture from invading the SiN film that constitutes the first sealing layer described above. In the attachment, the thermosetting adhesive was cured by performing a heat treatment at 100°C for 30 minutes, and in this way, an organic EL element was produced.

[0539] (6) Production of Display Device

[0540] (6.1) Production of Display Device 1

[0541] An adhesive layer was formed on the above-described color filter using a thermosetting adhesive used in the formation of the second sealing layer of the above-described organic EL element. Subsequently, the support glass of the first substrate of the organic EL element was peeled off by laser irradiation. Then, the first substrate surface of the organic EL element on which the varnish was exposed was brought together with the color filter, and heat treatment was performed at 100°C for 30 minutes, whereby the color filter was attached to the organic EL element.

[0542] The glass layer was attached to the surface opposite to the surface on which the organic EL element was attached of the color filter via the above-described adhesive layer. Subsequently, the above-described optical film 1 was attached to the surface opposite to the surface on which the color filter or the like was attached of the glass layer via the above-described adhesive layer, whereby the display device 1 was obtained. At this time, the optical film 1 was disposed so that the surface (B surface) having a higher indentation elastic modulus was on the side of the light emitting element. Note that the order of disposing the components of the display device 1 was in the order of the optical film 1, the adhesive layer, the glass layer, the adhesive layer, the color filter, and the organic EL element from the visible side.

[0543] (6.2) Production of Display Devices 2 to 4, 6 to 12, and 14 to 17

[0544] In the production of the above-described display device 1, the optical film was changed as described in Table II, and the display devices 2 to 4, 6 to 12, and 14 to 17 were obtained in the same steps.

[0545] (6.3) Production of Display Device 5

[0546] In the production of the above-described display device 1, the optical film 1 was disposed so that the surface (A surface) having a lower indentation elastic modulus was on the side of the light emitting element, and the display device 5 was obtained in the same steps.

[0547] (6.4) Production of Display Device 13

[0548] In the production of the above-described display device 1, the color filter was attached to the organic EL element in the same steps.

[0549] The above-described optical film 1 was attached to the surface opposite to the surface on which the organic EL element was attached of the color filter via the above-described adhesive layer, whereby the display device 13 was obtained. At this time, the optical film 1 was disposed so that the surface (B surface) having a higher indentation elastic modulus was on the side of the light emitting element. Note that the order of disposing the components of the display device 13 was in the order of the optical film 1, the adhesive layer, the color filter, and the organic EL element from the visible side.

[0550] 2. Evaluation

[0551] The indentation elastic modulus was measured for each of the obtained optical films. In addition, each of the display devices was evaluated as described below.

[0552] (1) Measurement of Indentation Elastic Modulus of Optical Film

[0553] Each of the optical films obtained above was cut into about 2 cm square, and the opposite surface of the measurement surface was fixed to a glass plate having a thickness of about 1 mm with an adhesive. Then, conditioning was performed by leaving the sample in an atmosphere of 23°C, 50% RH for 12 hours.

[0554] The indentation modulus of elasticity of the sample was measured using a dynamic ultra-micro hardness tester "DUH-211S" (manufactured by Shimadzu Corporation) with a test force of 12 mN. The indentation modulus of elasticity was measured at positions that were 10 equal parts from both ends in the width direction of the optical film. Among the measured values of the 9 points, the maximum and minimum values were excluded, and the arithmetic mean of the remaining 7 points was calculated.

[0555] The indentation modulus of elasticity was measured for each of the front and back surfaces of the optical film. Then, the surface having the higher indentation modulus of elasticity was taken as the A surface, and the surface having the lower indentation modulus of elasticity was taken as the B surface. The values of the indentation modulus of elasticity of the A and B surfaces were added and then divided by 2 to calculate the arithmetic mean.

[0556] (2) Visibility after the key test

[0557] The key test was performed on each of the display devices obtained above using a key tester with a load of 2.5 N, a number of key presses of 150,000 times, a key speed of 150 times / minute, and a knocking tool made of silicone rubber (φ 25 mm).

[0558] Each of the display devices after the key test was caused to display a black image. Then, the front surface reflectance was measured using a spectrophotometer "CM-2600d" (manufactured by Konica Minolta Holdings, Inc.), and evaluated based on the following criteria. Note that if the evaluation was A or higher (AAA to A), the display device could be practically used.

[0559] AAA: 1.5 or less.

[0560] AA: more than 1.5 and 1.6 or less.

[0561] A: more than 1.6 and 1.7 or less.

[0562] B: more than 1.7 and 1.8 or less.

[0563] C: more than 1.8.

[0564] (3) FOLDING RESISTANCE

[0565] Each of the display devices obtained above was subjected to 300,000 times of loadless bending test at a diameter of 3 mm. Then, each optical film was confirmed for presence or absence of a crease by visual observation. Further, the front surface luminance (luminance measured from the normal direction of the display image) of the display image from a distance of 1 m was measured using a spectroradiometric luminance meter "CS2000" (manufactured by Konica Minolta Sensing). Evaluation was performed based on the following criteria. Note that if the evaluation was A or more (AA to A), practical application was possible.

[0566] AA: No crease was confirmed even when the display device displayed an image having a peak luminance of 800 cd / m 2

[0567] A: No crease was confirmed even when the display device displayed an image having a peak luminance of less than 800 cd / m 2 2 However, if an image having a display luminance of 800 cd / m or more was displayed, a slight crease was confirmed. Note that the reduction rate of luminance was within 10%. However, there was no problem on the product.

[0568] B: A crease was confirmed regardless of the luminance of the image displayed by the display device. Note that the reduction rate of luminance exceeded 10%.

[0569] The results of measurement of the indentation elastic modulus of each optical film and the evaluation results of the display device are shown in Table II.

[0570] Note that in any of the optical films, the A face was the face that contacted the stainless steel belt support body at the time of production of the optical film.

[0571] Further, with respect to the crease resistance of Comparative Example 4, the optical film 15 was broken during the middle of the bending test, and evaluation was not possible.

[0572] [Table 2]

[0573] Table II

[0574]

[0575] As is clear from the examples and comparative examples, the display device of the present application can have both visibility after the key test and crease resistance.

[0576] As is clear from the examples and comparative examples, by making the arithmetic mean of the indentation elastic moduli of the front surface and the back surface of the optical film within the range of 5.0 to 10.0 GPa, it is possible to have both visibility after the key test and crease resistance.

[0577] ​​From the comparison between Example 1 and 5, it was found that, in the optical film, by disposing the surface having a lower indentation elastic modulus on the light emitting element side, it was possible to improve the visibility after the key test.

[0578] From the comparison between Example 1 and 13, it was found that, by further providing the display device with a glass layer between the optical film and the color filter, it was possible to improve the visibility after the key test.

[0579] From the comparison between Example 1 and 9 to 12, it was found that, by making the filler of the metal oxide be aluminum oxide, it was possible to achieve both the visibility after the key test and the folding resistance.

[0580] From the comparison between Example 1 and 4, it was found that, by making the content of the filler of the metal oxide or the metal salt be in the range of 1 to 30 mass% with respect to the total mass of the optical film, it was possible to achieve both the visibility after the key test and the folding resistance.

[0581] Industrial applicability

[0582] By using the present application, it was possible to provide a display device, an optical film, and a manufacturing method of an optical film, which achieved both the visibility after the key test and the folding resistance. As a result, it was possible to provide a flexible display which maintained a good visibility even when the operation of directly contacting and tapping or pressing with a finger or a stylus was performed.

[0583] Explanation of symbols

[0584] 1 Optical film

[0585] 2 Color filter

[0586] 3 Light emitting element

[0587] 4 Adhesive layer

[0588] 5 Glass layer

[0589] 10 Display device

[0590] 21 Carrier substrate

[0591] 22 Thin film glass

[0592] 23 Contact film

[0593] 24 Electromagnetic radiation

[0594] 41 Cathode

[0595] 42 Light emitting layer

[0596] 43 Transparent electrode

[0597] 44 Glass substrate

[0598] 45 White light

[0599] 46 RGB color filter

[0600] 47 blue light

[0601] 48 color filter (wavelength conversion film)

[0602] 49 stacked organic electroluminescence element

[0603] 51 black matrix

[0604] 52 transmissive region

[0605] 53 irradiation region

[0606] 60 color filter

[0607] 61 blue light

[0608] 62 green light

[0609] 63 red light

Claims

1. A display device comprising at least a light-emitting element and a color filter, characterized in that: The display device has an optical film. The optical film contains cellulose acetate and a filler of a metal oxide or a metal salt. The degree of substitution of acetyl groups in the cellulose acetate is in the range of 2.3 to 3.

0. The aspect ratio of the metal oxide or metal salt filler is in the range of 110 to 2000.

2. The display device according to claim 1, wherein The arithmetic mean of the indentation elastic moduli of the front and back surfaces of the optical film is within a range of 5.0 to 10.0 GPa.

3. The display device according to claim 1, wherein In the optical film, the surface having a low indentation elastic modulus is arranged on the light emitting element side.

4. The display device according to claim 1, wherein The display device is configured with the optical film, the color filter, and the light-emitting element in this order.

5. The display device according to claim 1, wherein The display device further includes a glass layer between the optical film and the color filter.

6. The display device according to claim 1, wherein The metal oxide is aluminum oxide.

7. The display device according to claim 1, wherein The content of the metal oxide or metal salt filler is in the range of 1 to 30% by mass relative to the total mass of the optical film.

8. The display device according to claim 1, wherein The light emitting element is an organic electroluminescent element, The display device is flexible.

9. The display device according to claim 8, wherein The color filter has a function of preventing reflection of light incident from the outside.

10. An optical film for a display device, characterized in that: The optical film contains cellulose acetate and a filler of a metal oxide or a metal salt. The degree of substitution of acetyl groups in the cellulose acetate is in the range of 2.3 to 3.

0. The aspect ratio of the metal oxide or metal salt filler is in the range of 110 to 2000, and The display device includes a color filter having a function of preventing reflection of light incident from the outside.

11. A method for producing an optical film, comprising producing the optical film according to claim 10, wherein: have: a process for preparing a slurry containing the cellulose acetate and a filler of a metal oxide or a metal salt, The process of casting the dope on a support to form a cast film, a step of peeling the cast film from the support, and a step of drying the cast film.

12. The method for manufacturing an optical film according to claim 11, wherein: The cast film is dried by heating.

Citation Information

Patent Citations

  • Optical compensatory sheet and liquid crystal display

    EP0911656A2

  • Protective film for polarizing film

    JP1994148430A

  • Production of mixed fatty acid ester of cellulose

    JP1998045804A

  • Cellulose acylate preparation and cellulose acylate film

    JP2006002025A

  • Cellulose acylate preparation and cellulose acylate film

    JP2006002026A

Cited By

  • Cellulose ester derivative modified alumina, and preparation method and application thereof

    CN122483713A